Cost-Effectiveness and EdTech: Considerations and case studies - Chuang, Rachel; Burnett, Nicholas; Robinson, Elizabeth (EdTech Hub, 2021)
The answer to the question ‘What is cost-effective EdTech?’ is highly nuanced, as it depends on the choice of the initiative, its design, implementation, intended audience, and how the local context is addressed. We compiled select case studies that examine how EdTech was used in cost-effective and less cost-effective ways. An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

How Can Decision-Makers Assess EdTech Interventions for Cost-Effectiveness to Enable Better Investments? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how decision-makers should consider cost-effectiveness when contemplating investing in EdTech programmes. Cost-effectiveness is a critically important consideration for anyone planning investments in EdTech, but it is also a complex one, which requires understanding the total cost of an intervention and comparing it against the likely impact on education. We draw on work from EdTech Hub and other prominent researchers to distil key practical insights for decision-makers on how to apply cost-effectiveness analysis to their decision-making. Practical considerations include recommendations on gathering the right data for analysis; ensuring cost calculations are holistic; leveraging existing frameworks and tools for cost and impact calculations; and ensuring that comparisons are made against non-tech interventions as well as the broader resource envelope available for education to determine affordability in a given context. Finally, we explore areas where additional work is needed, including an increased understanding of the challenges faced by decision-makers in considering cost-effectiveness and the need for greater transparency and accountability in cost-effectiveness analysis in the sector. Keywords Cost-effectiveness; EdTech; education policy; total cost of implementation; affordability; Learning-Adjusted Years of Schooling An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Assessing cost-effectiveness with equity of a programme targeting marginalised girls in secondary schools in Tanzania - Sabates, Ricardo; Rose, Pauline; Alcott, Benjamin; Delprato, Marcos (Journal of Development Effectiveness, 2021)
Cost-effectiveness studies rarely pay explicit attention to whether resources are used effectively to benefit the most marginalised. By linking a quasi-experimental design with detailed financial information, we analyse the cost-effectiveness of the Campaign for Female Education (CAMFED)’s programme in Tanzania. The programme provides targeted, multi-dimensional support to marginalised girls in government secondary schools in deprived rural areas. We find the cost-effectiveness of CAMFED’s programme to be similar to interventions designed for more advantaged populations who are easier (and less costly) to reach. There is further evidence of positive spill-over effects to boys in the schools supported by CAMFED.
Keywords: Cost effectiveness; Girls’ Education; Tanzania; equity

Assessing cost-effectiveness with equity of a programme targeting marginalised girls in secondary schools in Tanzania - Sabates, Ricardo; Rose, Pauline; Alcott, Benjamin; Delprato, Marcos (Journal of Development Effectiveness, 2021)
Cost-effectiveness studies rarely pay explicit attention to whether resources are used effectively to benefit the most marginalised. By linking a quasi-experimental design with detailed financial information, we analyse the cost-effectiveness of the Campaign for Female Education (CAMFED)’s programme in Tanzania. The programme provides targeted, multi-dimensional support to marginalised girls in government secondary schools in deprived rural areas. We find the cost-effectiveness of CAMFED’s programme to be similar to interventions designed for more advantaged populations who are easier (and less costly) to reach. There is further evidence of positive spill-over effects to boys in the schools supported by CAMFED.
Keywords: Cost effectiveness; Girls’ Education; Tanzania; equity

Session 6: How do I ensure my EdTech investments are cost-effective? - Chuang, Rachel; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Cost-Effective EdTech Paper 2: Good practice - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Cost-effectiveness of digital personalised learning: Three interventions from Kenya - Anonymised for Peer Review (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Cost-Effective EdTech Paper 1: A position piece on how the sector can make progress - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Cost-effective approaches to improve global learning: What does recent evidence tell us are “Smart Buys” for improving learning in Low and Middle Income Countries? - World Bank; Foreign, Commonwealth & Development Office; BE2 (2020)
Cost-Effective Approaches to Improve Global Learning : What Does Recent Evidence Tell Us Are “Smart Buys” for Improving Learning in Low and Middle Income Countries? (English)

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted; computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning; ⛔ No DOI found

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Low-cost educational messaging in West Africa: evidence on cost-effectiveness - Mitchell, Joel; Mukankusi, Aimée; D'Rozario, Jonny (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Smart buys, great sales and special offers: cost-effective approaches to improve global learning - Lewin, Keith; Learning | 0; Learning | 0 (The Education and Development Forum (UKFIET), 2020)

Remote Supervision Options for School Quality Assurance Officers: Recommendations for a cost-effective and rapid develop-and-test process - Beoku-Betts, Iman; Ampofo, Rudolph; Haßler, Björn (EdTech Hub, 2024)
The Sierra Leone Secondary Education Improvement Programme II (SSEIP II) is a five-year programme funded by the UK Foreign, Commonwealth and Development Office (FCDO) to support the Ministry of Basic and Senior Secondary Education (MBSSE) to improve learning outcomes for students at secondary level and to increase the enrolment, retention and well-being of girls and children with disabilities in school. Part of the programme includes exploring the use of different digital tools for School Quality Assurance Officers (SQAOs), including tools for remote visits. In December 2022, the EdTech Hub collaborated with the Government of Sierra Leone and implementing partners of the Leh Wi Lan programme (continued under SSEIP II) to better understand what factors affect the variability in the activity levels of SQAOs and the level of engagement with digital tools by school principals. Based on the findings of this research, the SSEIP II project will look at supporting the MBSSE to formalise remote supervision options for the SQAOs, particularly for those with remote clusters. As part of this work, this report focuses on recommendations for how SQAOs can conduct remote school visits, particularly for schools in hard-to-reach areas.An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Cost Effective Approaches to Improve Global Learning What Does Recent Evidence Tell Us Are Smart Buys for Improving Learning in Low-and-Middle-Income Countries - Global Education Evidence Advisory Panel (World Bank; FCDO; Building Evidence in Education, 2020)

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

The Effect of Computer-Assisted Learning on Students’ Long-Term Development - Bianchi, Nicola; Lu, Yi; Song, Hong (Social Science Research Network, 2020)
In this paper, we examine the effect of computer-assisted learning on students’ long-term development. We explore the implementation of the “largest ed-tech intervention in the world to date,” which connected China’s best teachers to more than 100 million rural students through satellite internet. We find evidence that exposure to the program improved students’ academic achievement, labor performance, and computer usage. We observe these effects up to ten years after program implementation. These findings indicate that education technology can have long-lasting positive effects on a variety of outcomes and can be effective in reducing the rural–urban education gap.
Keywords: China; computer-assisted education; education policy; education quality; education technology

The relationship between educational television and mathematics capability in Tanzania - Watson, Joe; Hennessy, Sara; Vignoles, Anna (British Journal of Educational Technology, 2021)
Previous studies have often demonstrated that educational television can have a positive effect on learning outcomes in low-income countries when delivered in controlled settings. However, existing research in low-resource contexts has scarcely considered the association between child outcomes and viewing in usual environments (ie, at their home, a friend’s home or a relative’s home). This lack of research is striking, as evidence from controlled settings might provide limited information on the effects of normal television exposure. This paper, therefore, investigates the relationship between normal exposure to a popular Tanzania-produced cartoon, Ubongo Kids and mathematics capability, as represented by plausible values derived from an item response theory model applied to children’s test responses. Cross-sectional investigation of a sample of 38 682 Tanzanian children suggested normal educational television exposure to be significantly associated with mathematics capability, when controlling for age, sex, school enrolment, Kiswahili attainment and household fixed effects. While cross-sectional results are not necessarily causal, the findings in this paper broadly correspond with those from previous designs using repeated observations. What is more, considering association results alongside cost and viewership estimates suggests television-based interventions to be highly cost effective. Practitioner Notes What is already known about this topic National data for Tanzania suggests the country to have both low levels of mathematics proficiency and considerable access to television technology. Educational television-based interventions might, therefore, be worthy of consideration by educational policymakers, especially given that studies conducted in controlled settings indicate that television can deliver learning benefits. There is, however, little evidence concerning educational television exposure outside of controlled settings. Only one such study in a low-income context that concerned the association between learning outcomes and viewing among primary-age children has been identified. What this paper adds This paper addresses this dearth of research by investigating the association between normal exposure to a Tanzanian cartoon, Ubongo Kids and mathematics capability, as derived from an item response theory model applied to the test responses of 38 682 children. Cross-sectional findings suggest the association between normal television exposure and mathematics capability to be significant. Further, a cost-effectiveness comparison with alternate interventions in comparable contexts indicates that educational television is highly cost-effective. Implications for practice and/or policy The findings presented in this paper concerning educational television viewership in usual environments act to triangulate those from prior research conducted in controlled settings. As such, policymakers in low-income contexts now possess more convincing evidence on the potential influence of educational television interventions. Additionally, the cost-effectiveness comparison made suggests that educational television should be considered a viable option by policymakers seeking to address learning outcomes with limited resources.
Keywords: Tanzania; cost effectiveness; educational television; mathematics

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

The relationship between educational television and mathematics capability in Tanzania - Watson, Joseph; Hennessy, Sara; Vignoles, Anna (British Journal of Educational Technology, 2020)
Previous studies have frequently demonstrated that educational television viewing can have a positive effect on learning in low-income country contexts when shows are delivered in controlled settings. However, the consequence of day-to-day viewing in such contexts has scarcely been considered. Additionally, no recent published research has provided any information on the costs of educational television. The lack of research in these areas is striking. Examining educational television viewing in monitored settings provides limited information on the influence of routine television consumption. Further, the broad reach of numerous educational television programmes should provide low perviewer costs and, resultantly, strong cost-effectiveness findings. This PhD study therefore examined (1) the association between educational television exposure and mathematics capability and (2) the cost effectiveness of educational television interventions. To achieve this, research was carried out that centred on Ubongo Kids – a popular Tanzanian-produced show delivering mathematics-focused content.
Keywords: Tanzania; ___working_potential_duplicate; cost effectiveness; educational television; mathematics; ⛔ No DOI found

How to Improve Education Outcomes Most Efficiently? A Comparison of 150 Interventions Using the New Learning-Adjusted Years of Schooling Metric - Angrist, Noam; Evans, David K.; Filmer, Deon; Glennerster, Rachel; Rogers, F. Halsey; Sabarwal, Shwetlena (Policy Research Working Papers, 2020)
Many low- and middle-income countries lag far behind high-income countries in educational access and student learning. Limited resources mean that policymakers must make tough choices about which investments to make to improve education. Although hundreds of education interventions have been rigorously evaluated, making comparisons between the results is challenging. Some studies report changes in years of schooling; others report changes in learning. Standard deviations, the metric typically used to report learning gains, measure gains relative to a local distribution of test scores. This metric makes it hard to judge if the gain is worth the cost in absolute terms. This paper proposes using learning-adjusted years of schooling (LAYS)—which combines access and quality and compares gains to an absolute, cross-country standard—as a new metric for reporting gains from education interventions. The paper applies LAYS to compare the effectiveness (and cost-effectiveness, where cost is available) of interventions from 150 impact evaluations across 46 countries. The results show that some of the most cost-effective programs deliver the equivalent of three additional years of high-quality schooling (that is, schooling at quality comparable to the highest-performing education systems) for just $100 per child—compared with zero years for other classes of interventions.
Keywords: Cost-Benefit Analysis; Education Outcomes; Government Policy; Impact Evaluation; Learning Loss; Learning-Adjusted Years of Schooling; Public Expenditure; Years of Schooling; ___working_potential_duplicate; ⛔ No DOI found

Reimagining Girls' Education: Solutions to keep girls learning in emergencies - Guglielmi, Silvia; Jones, Nicola; Nicolai, Susan; Pereznieto, Paola; Plank, Georgia; Vu, Nhung; Sanchez-Tapia, Ingrid; Mackintosh, Alasdair (UNICEF, 2021)
Keywords: Access to Education; Barriers; Context Effect; Cost Effectiveness; Costs; Disadvantaged Youth; Distance Education; Educational Finance; Educational Technology; Emergency Programs; Equal Education; Evidence Based Practice; Females; Foreign Countries; Gender Bias; Inclusion; Intervention; Planning; Sex Fairness; Sex Stereotypes; Teaching Methods; Technology Uses in Education

Should we paint all classroom roofs white to improve learning in Tanzania? - Proctor, Jamie (2022)
A growing literature base has developed from Global North contexts, showing a clear link between classroom temperature and student learning outcomes. However, very little evidence shows how this impact translates to low- and middle-income countries (LMICs), where average classroom temperatures are often high. The hypothesis for the research was that classroom temperatures in Tanzania are high and that a white-paint-cool-roof intervention would help mitigate these high temperatures. This study includes a literature review to understand the classroom policy in Tanzania, establish links between temperature and learning, and assess temperature retrofit options. Following this, the study presents the results of an experiment to trial a white-paint cool roof against a blue-paint roof and an unpainted control roof. Finally, data analysis predicts the intervention effects over an entire year and the subsequent impact on learning outcomes. The learning outcomes analysis includes a cost-effectiveness analysis using the Learning-Adjusted Years of Schooling (LAYS) metric. Empirical evidence of temperatures inside classrooms in Dar Es Salaam suggests that the temperature often exceeds 40℃. Literature searches indicate that this is the first time classroom air temperatures have been recorded and published for East Africa. The experiment involved using a low-cost retrofit intervention to reduce temperature – by painting the classroom roof blue or white over eight days. Results showed that the White Paint Intervention (WPI) reduced the temperature by around 3.7℃ over the course of the school day and up to a maximum of 5℃. The WPI was roughly twice as effective as the Blue Paint Intervention at reducing interior air temperatures. The WPI results were then modelled to estimate the classroom temperature reduction over a year, based on the assumed 3.5℃ reduction. Finally, using estimates from the existing literature, the learning impact of the intervention was calculated. The results suggest that using the WPI intervention can improve learning by 7.1%, which translates to an estimated 3.2 LAYS per classroom per year, at a cost-effectiveness of 5.3 LAYS per USD100. The paper shows that the impact of high temperatures in classrooms is likely undermining the funding currently channelled to improve learning outcomes in the region. Further, a WPI retrofit intervention is effective at reducing classroom temperatures in Tanzania. Due to climate-change-induced temperature increases, the intervention effectiveness is likely to increase over the coming decades. This paper was submitted as a dissertation in fulfilment of an MSc in Sustainability and Adaptation in the Built Environment at the Centre for Alternative Technology, Machynlleth, Powys (Wales)
Keywords: _r:AddedByZotZen

Data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia - Vijil, Alejandra; El-Serafy, Yomna; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2024)
This report provides a landscape analysis of available data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia. Digital data collection has the potential to facilitate cost-effective, adaptable, timely and reliable data to inform decision-making. The value proposition of these tools, as opposed to paper-based data collection, is that they have the potential to save valuable time and resources, minimise errors, and facilitate the sharing of results. To develop this report, we reviewed 50 available tools, of which we reviewed four in depth, considering their uses, features, and challenges. This report offers key takeaways on the potential advantages and limitations of using digital data collection tools in the education sector in sub-Saharan Africa and South Asia. Key words: data collection, data visualisation, education, sub-saharan africa, south asia, landscape analysis An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Effective and scalable math support: Experimental evidence on the impact of an AI-math tutor in Ghana - Henkel, Owen; Horne-Robinson, Hannah; Kozhakhmetova, Nessie; Lee, Amanda (Springer Nature Switzerland, 2024)
This study is a preliminary evaluation of the impact of receiving extra math instruction provided by Rori, an AI-powered math tutor accessible via WhatsApp, on the math performance of approximately 500 students in Ghana. Students assigned to both the control and treatment groups continued their normal classes with identical curricula and classroom hours. Students in the treatment group were given access to a phone for one hour a week – during their study hall period – and were allowed to use Rori to independently study math. All other aspects of the groups’ in-school experience were the same. We find that the math growth scores were substantially higher for the treatment group and statistically significant (p < 0.001). The effect size of 0.36 is considered large in the context of educational interventions: approximately equivalent to an extra year of learning. Importantly, Rori works on basic mobile devices connected to low-bandwidth data networks, and the marginal cost of providing Rori is approximately $5 per student, making it a potentially scalable intervention in the context of LMICs’ education systems. While the results should be interpreted judiciously, as they only report on year 1 of the intervention, they do suggest that chat-based tutoring solutions leveraging AI could offer a cost-effective and operationally efficient approach to enhancing learning outcomes for millions of students globally.

Template for costing remote learning encouragement - Blagrave, Holly Jean (2020)

Building effective COVID-19 Education Response Plans: Insights from Africa and Asia - Kimenyi, Eric; Otieno, Jennifer; Kaye, Tom (EdTech Hub, 2020)
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
Keywords: _EdTechHub_Output; _MELA_seen

Assessing cost-effectiveness with equity of a programme targeting marginalised girls in secondary schools in Tanzania - Sabates, Ricardo; Rose, Pauline; Alcott, Benjamin; Delprato, Marcos (Journal of Development Effectiveness, 2020)

Cost Measurement Guidance Note for Donor-Funded Education Programming - Walls, Elena; Tulloch, Caitlin; Holla, Alaka (United States Agency for International Development, prepared for Building Evidence in Education (BE2), 2020)

Cost Analysis Guidance for USAID-Funded Education Activities - Walls, Elena; Tulloch, Caitlin; Harris-Van Keuren, Christine (United States Agency for International Development, 2020)

Design-Based Implementation Research Baseline Data Collection: Technical report - Koomar, Saalim; Adam, Taskeen; Massam, Winston Edward; Anthony, Gervace; Mrope, Winifrida Jacob; Mtenzi, Fredrick; Mwakabungu, Fika; Komba, Aneth; Hennessy, Sara; Barretto, Johnpaul (EdTech Hub, 2022)
This research study aims to investigate the effectiveness, cost-effectiveness, and sustainability of a tech-supported, decentralised, and school-based teacher continuous professional development (TCPD) model, to improve learning outcomes in rural Tanzanian primary schools. The research will test and iteratively improve the national TCPD model and roll-out (including the semi-structured Communities of Learning), as outlined in the Tanzanian National TCPD Implementation Plan (2021). We seek to understand the model’s effectiveness and the role that technology can play. The research team includes researchers from EdTech Hub, Aga Khan University, and the Tanzania Institute of Education. The study employs a Design-Based Implementation Research (DBIR) approach in the first phase and an experimental study in the second phase. Keywords: teacher professional development; EdTech; design-based implementation research; Tanzania; Community of Learning; school-based An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?”  As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Keywords: computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning

Texting Parents about Early Child Development: Behavioral Changes and Unintended Social Effects - Barrera, Oscar; Macours, Karen; Premand, Patrick; Vakis, Renos (Policy Research Working Papers, 2020)

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Investigating the Impact on Learning Outcomes Through the Use of EdTech During Covid-19: Evidence from an RCT in the Punjab province of Pakistan - Adil, Fareeha; Nazir, Rabia; Akhtar, Misbah (EdTech Hub, 2021)
The objective of the current study is to test the impact of low-tech solutions on maths, Urdu, and English scores for students in the underdeveloped district of Bahawalnagar, which is situated in the southern part of Punjab in Pakistan. The target population for this study is Grade 8 students attending private schools. We have tested the impact of three interventions, namely: Teaching at the right level (TaRL), Fortnightly assessments (FAS) Digital teacher training sessions (DTS) Our findings show a significant and positive ‘Intention to Treat’ (ITT) impact on Urdu and English scores of the students in the TaRL treatment group. The students increased their English and Urdu scores by 0.56 SD. However, we found no significant impact of the intervention on maths scores in the TaRL treatment group. Fortnightly assessments and digital teacher training sessions were also found to contribute to higher English scores of the students. However, we found no ITT impact on the maths and Urdu scores for these treatment groups. The Local Average Treatment Effect (LATE) analysis revealed positive and significant improvement in Urdu and English scores of the students in the TaRL treatment group. Key stakeholders whom we interviewed suggested that redesigning the curriculum and incorporating TaRL within this approach could facilitate enhancement in learning outcomes in students in deprived areas. Our findings are important to help inform policymakers on the importance of designing and implementing cost-effective, low-tech solutions to help reduce learning gaps. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

Teacher professional development and coaching in low-income countries: Overarching considerations for the use of technology - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This second paper offers a wider perspective with some overarching considerations.
Keywords: C:Low-income countries; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

Isolating the “Tech” from EdTech: Experimental Evidence on Computer Assisted Learning in China - Ma, Yue; Fairlie, Robert; Loyalka, Prashant; Rozelle, Scott (National Bureau of Economic Research, 2020)
EdTech which includes online education, computer assisted learning (CAL), and remote instruction was expanding rapidly even before the current full-scale substitution for in-person learning at all levels of education around the world because of the coronavirus pandemic. Studies of CAL interventions have consistently found large positive effects, bolstering arguments for the widespread use of EdTech. However CAL programs, often held after school, provide not only computer-based instruction, but often additional non-technology based inputs such as more time on learning and instructional support by facilitators. In this paper, we develop a theoretical model to carefully explore the possible channels by which CAL programs might affect academic outcomes among schoolchildren. We isolate and test the technology-based effects of CAL and additional parameters from the theoretical model, by designing a novel multi-treatment field experiment with more than four thousand schoolchildren in rural China. Although we find evidence of positive overall CAL program effects on academic outcomes, when we isolate the technology-based effect of CAL (over and above traditional pencil-and-paper learning) we generally find small to null effects. Our empirical results suggest that, at times, the “Tech” in EdTech may have relatively small effects on academic outcomes, which has important implications for the continued, rapid expansion of technologies such as CAL throughout the world.

Consolidated Feedback on Tanzania Higher Education University Strategic Investment Plans - Adam, Taskeen; Koomar, Saalim; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk Response provides feedback on 15 Tanzania University Strategic Implementation Plans (USIPs) submitted to the Word Bank’s Higher Education for Economic Transformation Project (HEET). The feedback is intended to enhance and strengthen the plans provided by universities such that the USD 300 million is allocated and spent most effectively.
Keywords: Helpdesk Response; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF; dode_eth-src-eth; dode_eth-trf2-dode

Teacher professional development and coaching in low-income countries: An evidence-informed conversation - Haßler, Björn; Moss, Caitlin (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This first paper offers a broad overview.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:m; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech for Education in Emergencies: A review of existing guidance and minimum standards - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Hayat, Amal; Emerusenge, Aime Parfait; Zazai, Rozina (EdTech Hub, 2024)
EdTech Hub is seeking to work with the education in emergencies (EiE) sector to develop quality standards and guidance relating to the effective implementation of educational technology (EdTech) in crisis contexts. To ensure that this work is genuinely meaningful and helpful, it is important to understand what guidance is already available in this space, and what effective guidance could look like. To do this, we reviewed existing guidance documents relating to the design and implementation of EdTech in emergency contexts, along with materials from adjacent disciplines such as humanitarian work and technology design and development. By identifying key commonalities and persistent gaps across these documents, we were able to suggest what future guidance relating to EdTech in emergencies should include, and how this guidance should be developed. Keywords: EdTech; education in emergencies; guidance; minimum standards An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Leveraging Existing Technology in Low-Resource Settings to Support Learning: Conceiving and developing implementation plans for schools - Hayat, Amal; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
This document serves as a practical guide for implementers and decision-makers on how available technologies can effectively support teaching and learning in schools worldwide. Drawing on existing evidence of successful EdTech interventions in low-resource settings, particularly within Southeast Asia, it offers guidance on the essential steps in the early phases of EdTech implementation. The report also provides recommendations for transitioning from the initial conception phase to developing a comprehensive implementation plan. Keywords: EdTech implementation guide; low-resource settings; ASEAN; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

The Maldives and Sri Lanka: Question & Answer Session - Adam, Taskeen; Kaye, Tom; Haßler, Björn (EdTech Hub, 2020)
EdTech Hub participated in a question and answer session in May 2020 for policymakers in The Maldives and Sri Lanka. The session focused on the challenges and issues in designing effective distance education programmes during the Covid-19 pandemic. This document provides answers to a list of 13 questions received from stakeholders.
Keywords: F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Guidance Note 5 Supporting the effective use of digital technologies for learning by refugees and displaced persons From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Teacher professional development and coaching in low-income countries: Practical considerations for the use of technology. - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This third paper offers a range of practical considerations.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:o; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2020)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64SDs and writing scores by 0.45SDs. A reduced-cost version instead yields statistically-insignificant reading gains and some large negative effects (-0.33SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.
Keywords: NULP; ___working_potential_duplicate

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2021)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64 SD and writing scores by 0.45 SD. A reduced-cost version instead yields statistically insignificant reading gains and some large negative effects (−0.33 SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2021)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64 SD and writing scores by 0.45 SD. A reduced-cost version instead yields statistically insignificant reading gains and some large negative effects (−0.33 SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.

Making the grade: The sensitivity of education program effectiveness to input choices and outcome measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2021)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64 SD and writing scores by 0.45 SD. A reduced-cost version instead yields statistically insignificant reading gains and some large negative effects (−0.33 SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

How Can EMIS be Designed and Implemented in Ways That Make Them Used and Useful? - Adam, Taskeen; Mitchell, Joel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at education management information systems (EMIS). EMIS are pivotal in educational administration, facilitating the digitisation of processes and data to enable informed decision-making. However, persistent challenges impede their effectiveness. We examine why it is vital to consider how EMIS are designed and implemented, particularly with regard to the needs and contexts of low- and middle-income countries (LMICs). We consider constraints in technical capacity, limited funding, and insufficient user engagement. We identify concrete, evidence-based recommendations for how to make EMIS useful and used more frequently based on current and recent research. To enhance EMIS efficacy, there is a need to underscore utility and usability, ensuring the collection of pertinent data and user-friendly interfaces. Furthermore, the social implications of EMIS data on individuals and communities must be considered in order to meet their needs. We also explore areas for further consideration and include lists of resources relevant to EMIS and questions and solutions to consider. Keywords: education management information systems (EMIS); low- and middle-income countries (LMICs); user-centred design; evidence-based decision-making; EdTech; educational administration. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Cost-Effective Technology Approaches to Improve Education Outcomes for Girls: Learning from 41 Girls’ Education Challenge projects - EdTech Hub (EdTech Hub, 2022)

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Cost-Effective Approaches to Improve Global Learning - Global Education Evidence Advisory Panel (2023)

Achieving Cost-Effective Instructional Coaching at Scale: Evidence from Senegal - Bagby, Emilie; Swift-Morgan, Jennifer; Niang, Ablaye; Upadhyay, Arjun (Chemonics International, 2022)

Outcomes-based funding in education: Assessing cost effectiveness and accountability - Government Outcomes Lab (2022)

Working Towards Education Success Using Data: A review of Ghana's journey towards improved learning outcomes using data - Radford, Kate; Ampofo, Rudolph (EdTech Hub, 2024)
The sub-Saharan Africa region is trapped in a learning crisis with devastating implications for children. The Covid-19 pandemic further exacerbated the situation, with children losing an estimated equivalent of an additional year’s learning. Not addressing the regional learning crisis will have a detrimental impact on economic development and well-being and risks restricting future national and regional economic growth and productivity and fuelling social unrest. Education research has shown that good quality education system data, when judiciously used, can support improved learning outcomes among a host of other positive impacts on national education systems. This case study is the first in a series documenting the journey of Ghana’s Ministry of Education towards the effective use of data to guide its decision-making for policy and practice. Keywords: data for decision making; data governance; data management; Ghana; education data systems; evidence-based policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech and Covid-19: lessons from around the world - Pellini, Arnaldo (EdTech Hub, 2021)
Arnaldo Pellini, Susan Nicolai, Moizza Binat Sarwar, Sam Wilson, Akanksha Bapna, Chris McBurnie, Adedoyin Adesina, Oladele Akogun, Ernest Ngabo, Hind Al-Hindawi, Ni Wayan Suriastini, Vollan Ochieng, Moses Ngware, Asma Rabi , Abdul Musawir, Clement Sefa-Nyarko, Edem Agbe , Rabia Tabassum, Amna Zaidi, Jeroen Groenewegen, Harish Doraiswamy, Sudhansu Sharma, Liangdi Xu In this blog we summarise four takeaways from a reflection…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Using AI to Automate the Literature Review Process in Education: A Topic Brief - Haßler, Björn; Hassan, Syed Mustafa; Klune, Christopher; Mansour, Hassan; Friese, Laila (EdTech Hub, 2024)
Systematic literature reviews are often conducted manually in many research organisations. This topic brief explores the use of AI to automate the literature review process in the field of EdTech in order to improve the speed and efficiency of creating literature reviews across the sector. The topic brief is guided by the following questions: What tools are available for organisations and projects to use to automate evidence reviews? How appropriate are existing tools? Are they easy to use? Do they have licensing or cost barriers? How advanced are these AI tools? What tools are other organisations using to present the best evidence quickly? Is there value in building a bespoke AI tool to help identify, review, and synthesise evidence for literature reviews on education in low- and middle-income countries (LMICs)? What are the pros and cons of building a bespoke AI tool focusing on education in LMIC versus using an already existing commercial product? What are the cost implications of the two options?
Keywords: _r:AddedByMyEducationEvidence

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Abstract Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Keywords: computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning

Stemming learning loss during the pandemic: A rapid randomized trial of a low-tech intervention in Botswana - Angrist, Noam; Bergman, Peter; Brewster, Caton; Matsheng, Moitshepi (SSRN Electronic Journal, 2020)
The COVID-19 pandemic has closed schools for over 1.6 billion children, with potentially long-term consequences. This paper provides some of the ﬁrst experimental evidence on strategies to minimize the fallout of the pandemic on education outcomes. We evaluate two low-technology interventions to substitute schooling during this period: SMS text messages and direct phone calls. We conduct a rapid trial in Botswana to inform real-time policy responses collecting data at four- to six-week intervals. We present results from the ﬁrst wave. We ﬁnd early evidence that both interventions result in cost-eﬀective learning gains of 0.16 to 0.29 standard deviations. This translates to a reduction in innumeracy of up to 52 percent. We ﬁnd increased parental engagement in their child’s education and more accurate parent perceptions of their child’s learning. In a second wave of the trial, we provide targeted instruction, customizing text messages to the child's learning level using data from the ﬁrst wave. The low-tech interventions tested have immediate policy relevance and could have long-run implications for the role of technology and parents as substitutes or complements to the traditional education system.
Keywords: Education; Human Capital; Technology; _COVID_DEAA-List; __C:filed:1; ___working_potential_duplicate

The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

COVID-19 is a serious threat to aid to education recovery | Global Education Monitoring Report - UNESCO (Global Education Monitoring Report, 2020)

Global EdTech market to reach $404B by 2025 - 16.3% CAGR. - HolonIQ (HolonIQ, 2020)

Multi-Sectoral Rapid Needs Assessment: COVID19 - Jordan - UNHCR; UNICEF; WFP (2020)

Ready4K - ParentPowered (2020)

SDG7: Data and Projections - International Energy Agency (IEA, 2020)

Value for Money Policy and Procedure - EdTech Hub (2020)

Virtual Roundtable on Structured Pedagogy - better purpose (2020)

World Development Indicators - World Bank (2021)

Technology in education in low-income countries: Problem analysis and focus of the Hub's work - Hennessy, Sara; Jordan, Katy; Hassler, Bjoern; Hollow, David; Brugha, Meghan; Jamieson Eberhardt, Molly; Sabates, Ricardo (2020)
An output by the EdTech Hub - #EdTechHub, https://edtechhub.org

Education Finance Watch 2021 - World Bank; UNESCO (Global Education Monitoring Report, 2021)

onetab - onebillion (2020)

Unlocking Talent - Unlocking Talent (2021)

Research - EdTech Hub (EdTech Hub, 2021)

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Teacher professional development in sub-Saharan Africa: Equity and scale - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (Embedding Social Justice in Teacher Education and Development in Africa, 2021)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
Keywords: Author:Haßler; Björn-CV-OECS; _yl:a; dode_eth-src-dode; dode_eth-trf2-dode

Nudges to Improve Learning and Gender Parity: Preliminary findings on supporting parent-child educational engagement during Covid-19 using mobile phones - Aurino, Elisabetta; Tsinigo, Edward; Wolf, Sharon (EdTech Hub, 2022)
Key words: parental education engagement; caregiver engagement; nudges; text messages; schooling; learning; Ghana; gender In this study we evaluate a digital intervention to improve low-literate caregivers’ engagement with their children’s education and development in rural Ghana during the Covid-19 pandemic. The programme was a text-message-based behavioural change intervention for parents / caregivers that aimed to improve caregiver engagement in children’s educational activities, caregiver beliefs about returns to education, as well as children’s learning, enrollment, attendance, and gender parity in education. This household-randomised trial, conducted in the North East, Northern, Savannah, Upper East, and Upper West regions of Ghana, tested four variations of the intervention, varying both duration and a gender-parity focus. Households were randomised to one of five conditions: (i) regular behavioural nudges, 12 weeks; (ii) gender-boost behavioural nudges, 12 weeks; (iii) regular behavioural nudges, 24 weeks; (ii) gender-boost behavioural-nudges, 24 weeks; or (v) control. The interventions were implemented from January to April 2021 (for the 12-week groups) and January to June 2021 (for the 24-week groups). We collected data at midline (April–June 2021) and endline (August–September 2021). Our preliminary results suggest that a short, light-touch, SMS-based intervention can change caregiver behaviours and child outcomes in a rural, low-literate sample. However, the results were complex and intervention effectiveness depended on the caregiver having minimum levels of schooling. For caregivers with no education (65% of the sample), the intervention only increased caregiver expectations on reaching the desired level of education, especially among girls, but reduced educational engagement and some measures of children’s school enrollment and attendance. Educational engagement among Ghanaian caregivers is low relative to peer countries (Bornstein & Putnick, 2012; McCoy et al., 2018). The findings suggest that caregivers may need a base level of capital and resource (e.g., exposure to formal education) to enact the messages and increase their educational engagement with their children. Without this base level of capital, messages may increase caregivers’ aspirations for their children without providing enough support to change educational investments in positive ways. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

2023 Cost-Effective Approaches to Improve Global Learning: What does recent evidence tell us are "Smart Buys" for improving learning in low- and middle-income countries? - Akeyampong, K; Andrabi, T; Banerjee, A; Banerji, R; Dynarski, S; Glennerster, R; Grantham-McGregor, S; Muralidharan, K; Piper, B; Ruto, S; Saavedra, J; Schmelkes, S; et al. (World Bank, 2023)
Keywords: ⛔ No INSPIRE recid found

2023 Cost-Effective Approaches to Improve Global Learning - What does recent evidence tell us are “Smart Buys” for improving learning in low- and middle-income countries? - Banerjee, A; Banerji, R; Andrabi, T; Dynarski, S; Glennerster, R; Grantham-McGregor, S; Muralidharan, K; Piper, B; Saavedra, J; Yoshikawa, H; Ruto, S; Schmelkes, S (World Bank Group, 2023)

Two-Thirds of Poorer Countries Are Cutting Education Budgets Due to COVID-19 - World Bank (World Bank, 2021)

COVID-19 and options for financing education - Read, Lindsay (Background paper prepared for the Save Our Future white paper Averting an Education Catastrophe for the World’s Children, 2020)

Jusoor’s WhatsApp-Assisted Learning Programme: Sprint Review 1. - Tutunji, Suha; Boujikian, Michèle; Carter, Alice; Atkinson, Grace (EdTech Hub Sprint Review, 2020)
Keywords: ___working_potential_duplicate

Reimagine Education – Summary Case for Investment - UNICEF (2020)

EdTech in Indonesia: Ready for Take-off? - Bhardwaj, Riaz; Yarrow, Noah; Calì, Massimiliano (World Bank Group, 2020)

Effective Teacher Education in Low-Connectivity Settings: A Curated Resource List - Koomar, Saalim; Allier-Gagneur, Zoé; McBurnie, Chris (EdTech Hub, 2020)
This list curates resources — both tools and initiatives — that can be adapted to support teacher education in low-connectivity settings, a prevailing challenge in Madagascar. Each example identifies the challenges; necessary prerequisites; pros and cons and; costs and impact assessment data where possible.
Keywords: C:Madagascar; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; W:Low connectivity and/or electricity; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; dode_eth-src-eth; dode_eth-trf2-dode

Computer-assisted instruction tools: A model to guide use in low-and middle-income countries - Kaye, Thomas; Ehren, Melanie (International Journal of Education and Development using Information and Communication Technology, 2021)
Learning outcomes in low- and lower-middle-income countries (LMICs) require significant improvement. With traditional reform efforts taking many years to realise results, education practitioners in LMICs are searching for innovative ways to rapidly strengthen learning outcomes. One tool showing promise is computer-assisted instruction (CAI). While a growing number of studies document CAI’s positive impacts on learning outcomes, others have found nil or negative effects. Research has yet to identify why these differences occur, and, most importantly, which factors must be in place to ensure that CAI contributes to improving learning outcomes. The aim of our research was to fill this gap in the research by developing a model highlighting those factors influencing the results of CAI interventions. Adopting a realist-informed methodology, we analysed 21 resources shared by 13 experts from around the world. We used the results of this analysis to develop a model that outlines key trends that facilitate and/or impede the deployment of CAI tools in LMICs. We find that key factors that should be considered when designing CAI interventions include the operating environment; stakeholder engagement; infrastructure; technological trust; CAI tool design; content curation/creation; student engagement; classroom integration; teacher capacity; student capacity; and data collection and use. This model highlights both these individual elements as well as noting how these elements interact. The model provides a foundation that can guide future research in this under-examined area.
Keywords: ⛔ No DOI found

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Makhalidwe Athu - Creative Association International (2021)

Makhalidwe Athu - Creative Association International (2021)

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, 2020)
Education for the most marginalised post‑COVID-19 Guidance for governments on the use of digital technologies in education Join us December 18 for the report launch! Click here to register. The UNESCO Chair in ICT for Development, with support from the EdTech Hub, developed this report and associated Guidance Notes in 2020 building on a series of regional and sectoral consultations…
Keywords: ___working_potential_duplicate

Save our future - Haßler, Björn; Sagun, Rose (2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodoODE

Research on the response to COVID19 - Haßler, Björn; Fitzpatrick, Rachael (BE2, 2020)
Presentation given at BE2, 2020-10-06.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _yl:u; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Session 5: How can I use EdTech to ensure that students are provided with quality educational content at the right level? - Mazari, Haani; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Sandboxes: our approach to systemic experimentation - Simpson, Lea (EdTech Hub, 2020)
What’s a sandbox you ask? First in the series, this blog explains what you need to know about the Hub’s approach to experimentation and innovation.
Keywords: F:Sandbox; LP: English; _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Session 4: How can I rapidly upskill my large teacher workforce? - Koomar, Saalim; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Blended and Hybrid Learning Initiatives: A curated list for El Salvador - Villavicencio, Xuzel; Coflan, Caitlin Moss (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF country office and Ministry of Education team of El Salvador that was submitted to the EdTech Hub Helpdesk in November 2021. The UNICEF team requested a curated list of global blended and hybrid initiatives with a focus on initiatives that have used a multimodal strategy, highlighting effective and ineffective practices. This report does not aim to cover every leading and innovative blended / hybrid initiative with relevance to the Salvadoran context. Rather, it presents a list of curated resources with examples of challenges, lessons learned, and teacher training approaches that can be used as a guide when designing a multimodal strategy for the education sector. Keywords: hybrid; blended; El Salvador; multimodal; teacher training; remote learning An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Educational Television: A Rapid Evidence Review - Watson, Joe; McIntyre, Nora (EdTech Hub, 2020)
This Rapid Evidence Review (RER) gives an overview of the recent literature concerning how the use of educational television might support children’s learning in low- and middle-income countries (LMICs). In this review, educational television is defined as television designed with research-based knowledge of how children use and understand television that systematically incorporates academic or social curricula into its content. In low-income contexts, educational television material could be delivered through videos played in schools that are supported by corresponding teacher guidance (e.g. the Mexican school-based T elesecundaria programme), or broadcast on public channels (e.g. the Tanzanian animation, Ubongo Kids). As such, certain educational television projects are capable of functioning even in circumstances where access to formal schooling facilities is restricted. This review therefore provides information that is particularly valuable in the context of the COVID-19 pandemic.
Keywords: L:English UXZJW5DR; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
Keywords: ⛔ No INSPIRE recid found

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

EdTech and Covid-19: 10 Things to Know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2021)
EDTECH AND COVID-19 10 THINGS TO KNOW Covid-19 has reshaped our world. In education, mass school closures have accelerated the global use of education technologies. Yet the benefits do not reach everyone. Since the start of the pandemic, EdTech Hub and its partners have been researching and applying evidence on what works in technology for education in different contexts. Here…
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Guidance Note 14 Partnerships with the private sector and civil society From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The global stakes of digitalization in education - Haßler, Björn (The global stakes of digitalization in education (Uganda), 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _zenodo:submitted

Technology Use for Teacher Professional Development in Low- and Middle-Income Countries: Recommendations for policy from a systematic review - D'Angelo, Sophia; Hennessy, Sara; Kreimeia, Adam; Koomar, Saalim; Cao, Lydia; McIntyre, Nora; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: Read; Teacher education and training; _r:AddedByZotZen

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo, Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Sandbox Handbook V.2.0 - EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Under the Hood of an EdTech Study in Kenya: Implementation challenges, successes, and lessons learnt - Büchel, Konstantin; Crossley, Colin; Cullen, Claire; Letsomo, Thato (EdTech Hub, 2023)
In the years following a global pandemic that left 1.6 billion learners out of school, the global learning crisis has grown more urgent. Governments worldwide have sought technology-enabled education platforms that can support higher quality, resilient education systems. One cheap and easy tool for delivering remote educational support is basic mobile phones, which represent a potentially cost-effective and remote platform for adapting a range of proven pedagogical methods. To do so successfully, programme delivery should consider three key factors that include (1) careful training on delivering pedagogical methods in a phone setting, (2) Appropriate monitoring systems to ensure weekly delivery fidelity and, (3) an appropriate data and/or delivery infrastructure to enable programme monitoring. If done successfully, mobile phone programmes can present education ministries with an efficient delivery option for quality education at a fraction of the cost of higher-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

How Can EdTech Support Primary School Learners with Disabilities in LMICs? Recommendations for Policy - Lynch, Paul; Singal, Nidhi; Francis, Gill A. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

What Should Ministries of Education Prioritise When Crafting Their Edtech Strategies? - Thinley, Sangay (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at priorities for governments and ministries of education when crafting EdTech Strategies. Interest in developing EdTech strategies related to operational targets and outcomes has increased over the past few years, especially in response to the learning disruptions caused by the Covid-19 pandemic. Evidence suggests that countries with established EdTech strategies were better equipped to respond to the pandemic and its effects due to their advanced preparation and readiness for large-scale remote learning. We examine the key principles for EdTech strategies, including the importance of focusing on learning outcomes, inclusivity, teacher training, costs, and contextual needs, among other factors. We draw on EdTech Hub's work in supporting several governments in designing and implementing EdTech strategies, as well as broader evidence from the field, to offer practical insights. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt, such as prioritising consultative processes of strategy development while focusing on multi-modal, problem-driven EdTech solutions and interventions guided by a unifying educational goal. We highlight areas that require further research, in particular questions related to cost-effective approaches to improving global learning, how governments can develop dynamic and iterative strategies, and the role of private sector partnerships in the successful implementation of EdTech strategies. Keywords: EdTech; education technology; education strategy; best practices for EdTech; EdTech planning An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Session 3: How can I develop an aligned and actionable EdTech strategy - Wyss, Natalie; Mbugua, Wanjiku; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

How countries are using edtech (including online learning, radio, television, texting) to support access to remote learning during the COVID-19 pandemic - World Bank (World Bank, 2020)
Examples of how countries are using edtech to support remote learning under COVID-19
Keywords: ___working_potential_duplicate

Summary Brief: Problem Analysis and Focus of EdTech Hub’s Work - EdTech Hub Team (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Guidance Note 4 Inclusion and accessible learning for people with disabilities From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Technology use for teacher professional development in low- and middle-Income countries: A systematic review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (Computers and Education Open, 2022)
Pre-service education and in-service teacher professional development (collectively termed teacher professional development or TPD here) can play a pivotal role in raising teaching quality and, therefore, learning outcomes for children and young people in low- and middle-income countries (LMICs). However, TPD opportunities in LMICs are limited, unsustained, and often not informed by recent research evidence, and outcomes are mixed. Educational technologies offer potential to enhance formally provided programmes and informal peer-learning forms of TPD. We present the first systematic review of the literature pertaining to technology-mediated TPD for educators of school-aged learners in LMICs, aiming to characterise appropriate and effective uses of technology along with specific constraints operating in those contexts. An in-depth synthesis of 170 studies was undertaken, considering macro-, meso- and micro-level factors during TPD design and implementation in the 40 LMICs represented. Volume of publications increased dramatically over the review period (2008–2020), indicating that the field is rapidly developing. Results largely showed benefits for teachers, but evidence for sustainability, cost-effectiveness or tangible impacts on classroom practice and student outcomes was thin. Promising, locally-contextualised forms of technology-mediated TPD included virtual coaching, social messaging, blended learning, video-stimulated reflection, and use of subject-specific software/applications. We report on the variable effectiveness of programmes and limited attention to marginalised groups. To maximise effectiveness of technology-enhanced TPD, the role of facilitators or expert peers is paramount – yet often glossed over – and the interpersonal dimension of teacher learning must be maintained. Recommendations are made for researchers, policymakers, teachers and teacher educators.
Keywords: Disability; ICT; Read; Referenced; Teacher education and training; Teacher professional development; What works evidence; _EdTechHub_Output; _MELA_knowledge_product; _MELA_seen; e-learning; low- and middle-income countries (LMICs); pedagogy; peer learning; teacher training; technology; ⛔ No DOI found

What is 'Nudging' and How Does it Change Behaviour in Education? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the behaviour change strategy of leveraging concise messages at strategic decision points (i.e., ‘nudging’) to influence the behaviour of a recipient towards a desired outcome. We focus on EdTech Hub’s work concerning nudge messaging. It builds on work from messaging interventions in Ghana and Kenya, linking these to the broader literature on the topic. It emphasises that although there is a strong and growing evidence base for nudge technologies, effective implementation remains dependent upon context-specific adaptation. It is not inevitable that nudge messaging interventions will lead to positive outcomes — indeed, outcomes are often mixed. It is therefore vital to understand the specific impacts of interventions on particular groups of recipients. We present findings and recommendations that should inform how nudging technologies in education are approached and what decision-makers need to consider in order to ensure uptake and minimise risks. Lastly, we explore areas that require further research, namely, the changing nature of nudging due to artificial intelligence, the safeguarding risks of nudging, persisting questions about cost-effectiveness, and how nudging can more specifically target learning. Keywords: Behavioural psychology; EdTech; education; messaging; nudging; participation An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

A five-part education response to the COVID-19 pandemic - Haßler, Björn; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2020)
In March 2020, many countries began to close schools to slow the spread of coronavirus. Education leaders have subsequently launched rapid response programmes, implemented measures to support system recovery and explored long-term reforms. This paper proposes a five-part approach to guide education leaders through this process.
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:i; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

School mapping and decision-making - Vijil-Morin, Alejandra; Godwin, Katie; Ramirez, Ana; Mackintosh, Alasdair; Haßler, Björn (GEM Report UNESCO, 2023)
Reliable and timely data is essential for decision-makers at all administrative levels to ensure inclusive, equitable, and quality education for all. Geospatial data has the potential to provide valuable insights across a range of areas of interest to the education sector, from identifying potential threats to schools and the education community, such as throughdata on natural disaster patterns, to supporting equitable allocation of resources based on data showing the remoteness of schools. However, the use of Geographic Information Systems (GIS) is not widespread in the education sector. In this paper, we shed light on the experiences of five country governments, one regional agency, one international initiative, one implementing partner and one private entity, all using GIS for education decision-making in Latin America, the Caribbean, and sub-Saharan Africa.This paper presents the findings from primary data collection and analysis of interviews with representatives from these organisations from August –December 2022. Across these countries, we identified two central applications of school geospatial data, which included education planning -which school mapping is a part of -and cross-sector coordination. Among the main challenges to effectively using school geospatial data to make decisions, we found significant issues with capacity building, funding, bridging the data, and policymaking. On the other hand, when school mapping was used effectively, it helped increase transparency and equity, intersectoral collaboration, cost-effectiveness, and accuracy and reliability. After comparing the seven cases, we concluded that two key enablers need to be in place to promote the impact of geospatial data on educational decision-making: ‘usability’ and ‘availability and openness’.
Keywords: _r:AddedByZotZen

Deploying an e-Learning Environment in Zanzibar: A Short Guide - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the MoEVT and the World Bank approached the EdTech Hub to explore the feasibility of implementing a Virtual Learning Environment (VLE). The parties agreed on three deliverables to support this work. 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of an e-learning system in Zanzibar. This presentation deck is the third deliverable.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Guidance Note 12 Ensuring rigorous monitoring and evaluation of initiatives using digital technologies in education for the most marginalised From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

The relationship between educational television and mathematics capability in Tanzania - Watson, Joseph (University of Cambridge, 2020)
Previous studies have frequently demonstrated that educational television viewing can have a positive effect on learning in low-income country contexts when shows are delivered in controlled settings. However, the consequence of day-to-day viewing in such contexts has scarcely been considered. Additionally, no recent published research has provided any information on the costs of educational television. The lack of research in these areas is striking. Examining educational television viewing in monitored settings provides limited information on the influence of routine television consumption. Further, the broad reach of numerous educational television programmes should provide low per-viewer costs and, resultantly, strong cost-effectiveness findings. This PhD study therefore examined (1) the association between educational television exposure and mathematics capability and (2) the cost effectiveness of educational television interventions. To achieve this, research was carried out that centred on Ubongo Kids – a popular Tanzanian-produced show delivering mathematics-focused content. Quantitative investigation into the association between educational television exposure and mathematics capability used nationally representative data, collected by Uwezo Tanzania. A household fixed-effects model showed that exposure to educational television was significantly associated with mathematics capability among children aged 7-16, when controlling for age, sex, school enrolment and Kiswahili attainment. Findings from this model were used in cost-effectiveness calculations, alongside cost data and an estimate of the number of Ubongo Kids viewers. Results compared favourably against those for other interventions, with calculations regarding Ubongo Kids’ ongoing activities suggesting it to have been more cost effective than any other intervention previously investigated using the same cost-effectiveness approach. These findings indicate that in low-income contexts: educational television programmes can aid learning; and, that directing a greater proportion of available educational resources towards educational television interventions may benefit educational outcomes.
Keywords: ___working_potential_duplicate

Artificial Intelligence and Education Systems in 2035: Fourteen trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in artificial intelligence (AI) that might occur over the next 10 years. It begins by capturing fourteen trends, relating to AI that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Education for the most marginalised post-COVID-19: Guidance for governments on the use of digital technologies in education – Act one - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

تكنولوجيا التعليم وجائحة كوفيد 19 - .10 أشياء يجب معرفتها - EdTech Hub Team (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Adverse consequences of school closures - UNESCO (UNESCO, 2020)
School closures - even when temporary - carry high social and economic costs. The disruptions they cause touch people across communities, but their impact is particularly severe for disadvantaged boys and girls and their families. Some of the reasons why school closures are so harmful are listed below. While the list is far from comprehensive, it helps clarify why school closures should matter to all of us. Interrupted learning: Schooling provides essential learning and when schools close, children and youth are deprived opportunities for growth and development.

‘6Ps’ audit tool - Rahman, Asad; Carter, Alice (EdTech Hub, 2022)
EdTech interventions so often fail to take into consideration the broader system they work within. EdTech Hub has created this tool to assess interventions and identify any gaps in the thinking that might stop an intervention from working. Keywords: innovation; education system; 6Ps; tool An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Syṡtemic Mixed-Methods Research — a conceptual framework for scalable EdTech research - Haßler, Björn; El-Serafy, Yomna; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Mapping and Analysing Digital Learning Platforms in Latin America and the Caribbean - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in October 2021. The UNICEF team requested a curated list of digital learning platforms in the Latin America and Caribbean (LAC) region and an analysis of a shortlisted series of platforms intending to explore their potential for at-scale implementation and impact. This report does not aim to cover every leading and innovative digital learning platform in the LAC region. Rather, it presents a list of promising platforms and discusses their design and implementation to explore their relevance and potential for at-scale impact. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Using Interactive Radio Instruction to Mitigate the Educational Impact of Covid-19: A curated resource list - McBurnie, Chris (EdTech Hub, 2020)
Interactive Radio Instruction (IRI) is a distance education tool that enables educators to use radio broadcasts to direct active learning in the home. This curated list of resources aims to inform and support the use of IRI to mitigate the educational impact of Covid-19.
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (#SaveOurFuture, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

External Validity: Four Models of Improving Student Achievement - Duflo, Annie; Kiessel, Jessica; Lucas, Adrienne (National Bureau of Economic Research, 2020)
Randomized controlled trials in lower-income countries have demonstrated ways to increase learning, in speciﬁc settings. This study uses a large-scale, nationwide RCT in Ghana to show the external validity of four school-based interventions inspired by other RCTs. Even though the government implemented the programs within existing systems, student learning increased across all four models, more so for female than male students, and many gains persisted one year after the program ended. Three of the four interventions had a similar cost eﬀectiveness. The intervention that directly targeted classroom teachers increased the likelihood that teachers were engaged with students.
Keywords: C:Ghana

What are countries doing that already use remote learning extensively? What can we learn from them? - Ndaruhutse, Susy; Gibbs, Emma; Fitzpatrick, Rachael (2020)
Keywords: H: Distance education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

EdTech to Support Blended Learning in Mozambique: A curated list of EdTech interventions - Flam, Rebekka; Ramesh Vasudevan, Sharanya; Coutrim, Erica (EdTech Hub, 2024)
This document was produced in response to a request from the UNICEF Mozambique country office submitted to the EdTech Hub Helpdesk in November 2023. The UNICEF team requested a curated list of blended learning approaches and resources that are relevant to the Mozambique context, with a special focus on resources that are implemented or sourced from the Eastern and Southern Africa region. In response, the EdTech Hub Helpdesk has created this report to provide contextual and background information on the blended learning landscape in Eastern and Southern Africa, with a specific focus on Mozambique, along with a list of resources on blended learning. Keywords: blended learning; hybrid learning; Africa; Mozambique An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Educational Technology in Developing Countries: A Systematic Review - Rodriguez-Segura, Daniel (EdPolicyWorks Working Paper, 2020)
Keywords: ___working_potential_duplicate

Determining the suitability of Whatsapp for Jusoor Azima Project - Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

TCPD in Tanzania: Design-Based Implementation Research Cycle 2 Recommendations - Chachage, Kristeen; Koomar, Saalim; Swai, Calvin; Massam, Winston; Hennessy, Sara; Masonda, Jonathan Paskali; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Frederick; Komba, Aneth; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the second cycle of the DBIR carried out between September and November 2023. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; Tanzania; communities of learningAn output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Deploying an e-learning Environment in Zanzibar: Digital Content Curation - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank approached EdTech Hub (the Hub) to explore the feasibility of implementing a Virtual Learning Environment (VLE). The MoEVT, the World Bank and the Hub agreed that the Hub would work with the MoEVT to develop the following 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of the e-learning system. This document addresses the second part of the request and is an elaboration of the digital content selection, curation, and adaptation process suggested in the first report. However, this document is a stand-alone piece that does not require familiarity with any of the other deliverables.
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Les Technologies De L’enseignement Et Le Covid-19 - 10 Choses À Savoir - EdTech Hub Team (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Guidance Note 8 Resilient and sustainable energy solutions From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Bandarban Sandbox: Needs assessment and hypothesis development - Tanweer, Rabia; Nashtaran, Trishia; Plaut, Daniel; Rahman, Asad; Ahmed, Shakil; Chowdhury, Dilruba; Rabbi, BM Fazley; Hoque, Rashedul; Nahar, Nurun; Afroze, Sadia (EdTech Hub, 2022)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners, working closely with the government and EdTech Hub to identify how EdTech can best be harnessed to support learning in Bangladesh. This partnership uses the sandbox approach — which provides a space for partners to test and grow ideas in conditions of uncertainty — to test how EdTech modalities that aim to improve numeracy outcomes for Grade 6 learners (early secondary) in Bandarban, one of the most remote areas of Bangladesh, can be used most effectively by learners and educators. This report outlines the process and findings from the needs assessment and hypothesis development phase. These findings (as well as the data collection which informs them) are organised around five research questions developed by EdTech Hub in partnership with Agami Education Foundation, the implementing agency for the sandbox. The findings of the research were distributed in themes that outlined the availability and utilisation of technology and a valid level of knowledge and interest in teachers and students towards using technology for education. While some findings shed light on the technical aspects of the context, some human factors also played a role in resisting the acceptance of technology in education. Building on the learning from this needs assessment phase, Agami Education Foundation and EdTech Hub have agreed to test this implementation plan in the upcoming staggered deployment phase. Keywords: EdTech; sandbox; numeracy; Bandarban; Bangladesh; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech for Girls' Education: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; D'Rozario, Jonny; Thinley, Sangay; Mazari, Haani; Hinks, Jessica (EdTech Hub, 2025)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for girls in Southeast Asia. The review summarises how EdTech is currently being used with girls in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech for girls' education. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for girls, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for girls. An output of the EdTech Hub, https://edtechhub.org/

Randomised Controlled Trial Protocol: Digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms - Major, Louis; Daltry, Rebecca; Otieno, Mary; Otieno, Kevin; Zhao, Annette; Hinks, Jessica; Sun, Chen; Friedburg, Aidan (EdTech Hub, 2023)
This protocol provides a detailed overview of a cluster-randomised controlled trial (RCT) being undertaken in pre-primary schools in Kenya. The RCT seeks to rigorously investigate the impact of a classroom-integrated digital personalised learning (DPL) tool on early grade numeracy and literacy learning outcomes. The protocol is being disseminated prior to endline data analysis to promote transparency and a comprehensive understanding of the RCT approach and design. This protocol was originally published in October 2023. This is an updated version where we have a) clarified that the sample size stated in Sections 2 and 2.2 is the 'pre-attrition' sample; and b) added a paragraph to Section 2.4.1 to provide further clarification regarding the use of code-switching. No changes to the analytical approach have been made. Keywords: digital personalised learning; DPL; Randomised controlled trial; RCT; research methodology; learning outcomes; Kenya An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Guidance Note 1 In the local context — using digital technologies to develop local content From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Summary: EdTech for Learners With Hearing and Visual Impairments - A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Learners With Hearing and Visual Impairments produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/.An output of the EdTech Hub, https://edtechhub.org/ An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Promising practices for equitable remote learning: Emerging lessons from COVID-19 education responses in 127 countries - Dreesen, Thomas; Akseer, Spogmai; Brossard, Matt; Dewan, Pragya; Giraldo, Juan-Pablo; Kamei, Akito; Mizunoya, Suguru; Ortiz, Javier Santiago (UNICEF, 2020)
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Smart buys: system reform, local-level buy-in and reaching the most marginalised - Ndaruhutse, Susy (The Education and Development Forum (UKFIET), 2020)
This blog was written by Susy Ndaruhutse, Chair of the Board of Trustees, UKFIET. Earlier this month, I listened with interest to representatives of the Global Education Evidence Advisory Panel (GEEAP) presenting a summary of the findings and recommendations from their latest report Cost-Effective Approaches to Improve Global Learning: What does recent evidence tell us […]

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

TCPD in Tanzania: Design-Based Implementation Research Cycle 1 Recommendations Policy Brief - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Frederick; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the first cycle of the DBIR carried out between September and December 2022. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; tanzania; communities of learning An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

India’s distance learning response to the COVID-19 crisis - Doraiswamy, Harish; Gupta, Gouri; Kamath, Dhruv; Sharma, Sudhanshu (Central Square Foundation, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Online Examinations in Emergency Contexts: Can Proctoring and Other Technologies Be Feasible Alternatives for Facilitating Inclusive School Exams for All in Emergency Contexts? - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; Al Mekdad, Bayan; Sabboura, Rani; Shequem, Yazeed (EdTech Hub, 2022)
The purpose of this document is to serve as a guide that education practitioners working in emergency contexts can use to assess the feasibility of implementing online examinations and using proctoring technologies. The implementation of online high-stakes examinations in Syria and other emergency contexts will require significant investments in achieving the prerequisites needed for feasibility and credibility. Prerequisites include electricity, internet, and devices, as well as the development of the digital skills necessary for students to participate in online exams and for teachers and administrators to facilitate online exams. Further efforts are needed to prevent leakage of information on exam questions and content, and promote cultural change around online examinations. Key words: online examinations; proctoring technologies; emergency contexts; Syria An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Deploying an e-Learning Environment in Zanzibar: Feasibility Assessment - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
The Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank (the Bank) approached the EdTech Hub (the Hub) in April 2020 to explore the feasibility of implementing a Virtual Learning Environment (VLE). The Hub was requested to focus primarily on the deployment of a VLE in lower secondary education, and this report consequently focuses primarily on this group. The report is structured in four sections: An introduction to provide the background and guiding principles for the engagement with a short overview of the methodology applied. An analysis of the Zanzibar education system with a particular focus on elements relevant to deploying a VLE. This includes the status of ICT infrastructure, and a summary of the stakeholders who will play a role in using or implementing a VLE. A third section that discusses types of VLEs and content organisation, and their applicability to the Zanzibar ecosystem. A conclusion with recommendations for Zanzibar, including short- and long-term steps. In this collaboration with Zanzibar’s MoEVT, the Hub team sought to understand the purpose of the proposed VLE. Based on discussions and user scenarios, we identified two main education challenges a VLE may help to resolve. In the short term, students cannot go to school during the COVID-19 crisis, but need access to educational content. There is content, but no flexible and versatile platform to disseminate content to all students. In the long term, a mechanism to provide students with access to quality, curriculum-aligned content in school, or remotely, is required.
Keywords: C:Tanzania; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

What steps are being taken to reach the most disadvantaged students during the period of Covid-19 school closure? - McAleavy, Tony; Joynes, Chris; Gibbs, Emma; Sims, Kate (Education Development Trust, 2020)
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Mango Tree Literacy Labs’ Radio Programme Sandbox - Esbeck, Craig; Oloa, Charles; Brown, Victoria; Plaut, Daniel; Salami, Taiye (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Experiment Types for EdTech - Rahman, Asad; Carter, Alice; WambûiKuria, Catherine; Mbugua, Ciku; Simpson, Lea; Kably, Nathan (EdTech Hub, 2022)
An EdTech Hub sandbox fast-tracks promising EdTech interventions by providing funding, tools, and access to evidence. It provides a space for partners to test and grow ideas in conditions of uncertainty. Since 2020, EdTech Hub has worked with partners in eight countries to test and grow EdTech based on our sandbox methodology. When testing and growing EdTech, this tool provides a non-exhaustive list of ways to design and run experiments. Keywords: sandbox; lean startup; lean impact; experiments; validation; prototype An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

Parent and Caregiver Engagement in Kenya: Gaps, opportunities, and emerging questions for future research - Flam, Rebekka; Honda, Delanie; Ramesh Vasudevan, Sharanya; Mbugua, Wanjiku (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: Helpdesk Response; _r:AddedByZotZen

Summary: EdTech for Girls’ Education - A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Hinks, Jessica; D'Rozario, Jonny; Thinley, Sangay (EdTech Hub, 2024)
This document is a summary of a Rapid Evidence Review on EdTech for Girls' Education produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Child education in the time of pandemic: Learning loss and dropout - Khan, Muhammad Jehangir; Ahmed, Junaid (Children and Youth Services Review, 2021)
The disruptive effects of the COVID-19 pandemic had affected the education sector at an unprecedented scale. In order to contain the spread of the virus, a large number of countries across the globe have shut their schools to handle the pandemic. However, it has adversely affected students’ learning and school attendance. In this regard, we assess the impact of COVID-19 on the learning loss, school dropout, and the economic costs in term of foregone earnings for children in Pakistan. The study finds a substantial decrease in Learning Adjusted Years of Schooling (LAYS) with worsening consequences for girls than boys. Likewise, the aggregate economic cost amounts to 107 billion dollars when adjusted for human capital utilisation. Besides, our simulation results suggest that about 7.2 million children dropout due to a reduction in household expenditure by 50 percent. In comparison, the dropout is more pronounced at the primary level of schooling. The results recommend that the government design robust social protection and remote education strategies to mitigate school closure’s adverse effect on children’s learning. The emphasis should be rather on the long run strategies to cope with a resilient education system of futuristic orientation.

EdTech in developing countries: a review of the evidence - Rodriguez-Segura, Daniel (The World Bank Research Observer, 2021)
The emergence of educational technology (“EdTech”) in developing countries has been received as a promising avenue to address some of the most challenging policy questions within educational systems. In this paper, I review and synthesize all existing studies with credible causal identification frameworks of EdTech interventions in developing countries. While other studies review the evidence for EdTech interventions in developed countries, there is currently no equivalent study for developing contexts, in spite of the rising number of studies being produced. I classify studies into four thematic categories based on the type of EdTech intervention analyzed: Access to technology; technology-enabled behavioral interventions; improvements to instruction; and self-led learning. I find that EdTech interventions centered around self-led learning and improvements to instruction are the most effective forms of EdTech at raising learning outcomes. Similarly, technology-enabled behavioral interventions are less promising for generating large effects but highly cost-effective given their typically low marginal costs. Although expanding access to technology alone is not sufficient to improve learning, it is a necessary first step for some other types of interventions. More broadly, the overall success of interventions rests on the thoughtful customization of the EdTech solution to the policy constraints at hand. Finally, EdTech interventions across all thematic areas can and should act as complements by leveraging their respective comparative advantages to address deficiencies within educational systems in developing countries.

EdTech and the COVID-19 response: A case study of Kenya - Ngware, Moses; Ochieng, Vollan (EdTech Hub, 2020)
Keywords: Kenya; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Optimising Session Duration on Digital Personalised Learning Tools for Early Grade Learners - Sun, Chen; Moustafa, Nariman; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the first in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the optimal number of minutes for pre-primary learners on a classroom-integrated digital personalised learning tool to optimise learning outcomes. The A/B/C test found different levels of session duration impacted on literacy and numeracy outcomes, with the findings for numeracy dependent on grade level. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; session duration An output of EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Teacher Motivation: Exploring non-financial incentives in school-based teacher professional development in Tanzania - Anonymised for Peer Review (EdTech Hub, 2025)
High-income countries often use external incentives such as remuneration, professional pathways or accreditation to motivate teachers to engage in professional development. This paper reflects on the challenges of engaging teachers in school-based professional development in resource-scarce education environments where the use of such incentives is not feasible and explores practical strategies to motivate their engagement. In such contexts, where qualified teacher status and promotion are not tied to engagement in professional development, other means for encouraging teachers to take up professional learning opportunities are paramount. In this two-year, iterative, design-based implementation research study of a national teacher professional development initiative in Tanzania, non-financial incentives were tested in eight rural schools. Findings show that completion certificates motivated teachers; achievement certificates had mixed results due to doubt around the fairness of the peer-review process. Additionally, teachers were intrinsically motivated by other changes in the programme such as access to relevant digital modules which allowed for teacher agency, and by increased collegial relationships and collaboration. Keywords: teacher motivation; school-based teacher professional development; design-based implementation research; Tanzania, non-financial incentives; intrinsic and extrinsic motivation An output of the EdTech Hub, https://edtechhub.org/
Keywords: Hide; _r:AddedByMyEducationEvidence

Child education in the time of pandemic: Learning loss and dropout - Khan, Muhammad Jehangir; Ahmed, Junaid (Children and Youth Services Review, 2021)
The disruptive effects of the COVID-19 pandemic had affected the education sector at an unprecedented scale. In order to contain the spread of the virus, a large number of countries across the globe have shut their schools to handle the pandemic. However, it has adversely affected students' learning and school attendance. In this regard, we assess the impact of COVID-19 on the learning loss, school dropout, and the economic costs in term of foregone earnings for children in Pakistan. The study finds a substantial decrease in Learning Adjusted Years of Schooling (LAYS) with worsening consequences for girls than boys. Likewise, the aggregate economic cost amounts to 107 billion dollars when adjusted for human capital utilisation. Besides, our simulation results suggest that about 7.2 million children dropout due to a reduction in household expenditure by 50 percent. In comparison, the dropout is more pronounced at the primary level of schooling. The results recommend that the government design robust social protection and remote education strategies to mitigate school closure’s adverse effect on children's learning. The emphasis should be rather on the long run strategies to cope with a resilient education system of futuristic orientation. (PsycInfo Database Record (c) 2021 APA, all rights reserved)
Keywords: Adjustment; COVID-19; Education; Learning Strategies; Learning loss; Pakistan; Pandemics; School Dropout; School Dropouts; School Learning

Ghana’s education response during the COVID-19 crisis: EdTech to the rescue? - Agbe, Edem; Sefa-Nyarko, Clement (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH

Key considerations when developing an ICT in Education strategy - AlSheikh Theeb, Thaer; Chuang, Rachel; Pandit, Sanjana (EdTech Hub, 2022)
This report was commissioned by UNICEF and produced under UNICEF and EdTech Hub’s global partnership, in response to a request from the UNICEF Laos team that was submitted to the EdTech Hub Helpdesk. It presents key considerations on the overarching process to develop an ICT in Education strategy (e.g., components, stakeholders, timelines) and lists examples of other national ICT in Education and EdTech strategies. Keywords: EdTech strategies; ICT in Education strategies An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Guidance Note 7 Ensuring resilient connectivity From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

School’s Out: Experimental Evidence on Limiting Learning Loss Using “Low-Tech” in a Pandemic - Angrist, Noam; Bergman, Peter; Matsheng, Moitshepi (National Bureau of Economic Research, 2020)
Schools closed extensively during the COVID-19 pandemic and occur in other settings, such as teacher strikes and natural disasters. This paper provides some of the first experimental evidence on strategies to minimize learning loss when schools close. We run a randomized trial of low-technology interventions – SMS messages and phone calls – with parents to support their child. The combined treatment cost-effectively improves learning by 0.12 standard deviations. We develop remote assessment innovations, which show robust learning outcomes. Our findings have immediate policy relevance and long-run implications for the role of technology and parents as partial educational substitutes when schooling is disrupted.
Keywords: ___working_potential_duplicate

Women's empowerment in action: Evidence from a randomized control trial in Africa - Bandiera, Oriana; Buehren, Niklas; Burgess, Robin; Goldstein, Markus; Gulesci, Selim; Rasul, Imran; Sulaiman, Munshi (American Economic Journal: Applied Economics, 2020)
We evaluate a multifaceted policy intervention attempting to jump-start adolescent women's empowerment in Uganda by simultaneously providing them vocational training and information on sex, reproduction, and marriage. We find that four years postintervention, adolescent girls in treated communities are more likely to be self-employed. Teen pregnancy, early entry into marriage/cohabitation, and the share of girls reporting sex against their will fall sharply. The results highlight the potential of a multifaceted program that provides skills transfers as a viable and cost-effective policy intervention to improve the economic and social empowerment of adolescent girls over a four-year horizon.
Keywords: Child Care; Children; Domestic Abuse, Fertility; Education and Economic Development, Marriage; Family Planning; Family Structure; Human Development; Income Distribution; Labor Productivity, Economic Development: Human Resources; Marital Dissolution; Migration; Non-labor Discrimination, Labor Demand, Human Capital; Occupational Choice; Skills; Youth, Economics of Gender

Investigating the Impact of Content Repetition on Digital Personalised Learning Tools for Early Grade Learners - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the third in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the impact of repeating learning content for pre-primary learners on learner device usage and learning outcomes. The A/B test found that content repetition had an impact on literacy and numeracy outcomes for PP2 learners. PP2 learners’ usage of the DPL tool was significantly reduced with content repetition. However, considering the small size of the mixed-methods sample, caution should be taken when interpreting these results. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; repetition An output of EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Designing Digital Notifications to Support Teacher Uptake of Data Dashboards - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the fourth in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the extent to which the provision of notifications to pre-primary teachers to view data dashboards impacts learner device usage and learning outcomes. The A/B/C test found no impact on device usage and negligible impact on learning outcomes. This suggests that accompanying data dashboards with notifications did not influence pedagogical practice in a way which impacted on learning. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; notification system An output of EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Building back better to avert a learning catastrophe: Estimating learning loss from COVID-19 school shutdowns in Africa and facilitating short-term and long-term learning recovery - Angrist, Noam; de Barros, Andreas; Bhula, Radhika; Chakera, Shiraz; Cummiskey, Chris; DeStefano, Joseph; Floretta, John; Kaffenberger, Michelle; Piper, Benjamin; Stern, Jonathan (International Journal of Educational Development, 2021)
We model learning losses due to the COVID-19 pandemic and the potential for cost-effective strategies to build back better. Data from Early Grade Reading Assessments in Ethiopia, Kenya, Liberia, Tanzania, and Uganda suggest half to over a year’s worth of learning loss. In modeling losses over time, we found that learning deficits for a child in grade 3 could lead to 2.8 years of lost learning by grade 10. While COVID-19 has stymied learning, bold, learning-focused reform consistent with the literature reviewed in this paper—specifically reform on targeted instruction and structured pedagogy—could improve learning even beyond pre-COVID-19 levels.
Keywords: COVID-19; Education; Foundational skills; Learning loss; Recovery

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Large Learning Gains in Pockets of Extreme Poverty: Experimental Evidence from Guinea Bissau - Fazzio, Ila; Eble, Alex; Lumsdaine, Robin L; Boone, Peter; Bouy, Baboucarr; Hsieh, Pei-Tseng Jenny; Jayanty, Chitra; Johnson, Simon; Silva, Ana Filipa (2021)
Children in many extremely poor, remote regions are growing up illiterate and innumerate despite high reported school enrollment ratios. Possible explanations for such poor outcomes include demand – for example, low perceived returns to education compared to opportunity cost; and supply – poor state provision and inability of parents to coordinate and finance better schooling. We conducted a cluster-randomized trial in rural Guinea Bissau to understand the effectiveness and cost of concerted supply-based interventions in such contexts. Our intervention created simple schools offering four years of education to primary-school aged children in lieu of the government. At endline, children receiving the intervention scored 58.1 percentage points better than controls on early grade reading and math tests, demonstrating that the intervention taught children to read and perform basic arithmetic, from a counterfactual condition of very high illiteracy. Our results provide evidence that particularly needy areas may require more concerted, dramatic interventions in education than those usually considered, but that such interventions hold great potential for increasing education levels among the world’s poorest people.

Remote Learning: Evidence from Nepal during COVID-19 - Radhakrishnan, Karthika; Sabarwal, Shwetlena; Sharma, Uttam; Cullen, Claire; Crossley, Colin; Letsomo, Thato; Angrist, Noam (World Bank, 2021)
This note discusses early results from a distance education program on foundational numeracy for primary school students in Nepal during Coronavirus (COVID-19) evaluated in a randomized trial. The trial included 3,700 households with children in public school (grades 3-5). It provided support for foundational numeracy through mobile phone-based tutoring. The trial tested delivery through public school teachers and also through NGO facilitators. It led to a 30 percent increase in foundational numeracy, with teachers being slightly more effective at producing learning gains than NGO facilitators. These results suggest that instructional support through mobile phones can be a high-access and low-cost approach to providing instruction at scale
Keywords: Coronavirus; Covid-19; Numeracy; Pandemic Impact; Remote Learning; School Closure

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Education in Conflict and Crisis in 2035: Twelve trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in the increase in global conflict and crises that might occur over the next 10 years. It begins by capturing twelve trends, relating to conflict and crisis, that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Pakistan Distance-Learning Topic Brief: Primary-level Deaf Children - Lynch, Paul; Kaye, Tom; Terlektsi, Emmanouela (EdTech Hub, 2020)
The Covid-19 crisis has severely impacted the ability of national education actors to provide access to education services for all students.This brief provides guidance and recommendations on how to support the education of deaf children in Pakistan using alternative learning approaches. It presents the rationale for adopting certain teaching and learning strategies when supporting the learning and well-being of deaf children during global uncertainty. Children with deafness and hearing loss are particularly vulnerable during school closures. They are isolated at home and unable to access information as easily as when attending school. This brief presents some of the practices that are reportedly working well for deaf children in different contexts.
Keywords: C:Pakistan; F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

SUMMARY Learning through the crisis: Helping decision-makers around the world use digital technology to combat the educational challenges produced by the current COVID-19 pandemic - Traxler, John; Scott, Howard; Smith, Matt; Hayes, Sarah (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Short and Long-Run Distributional Impacts of COVID-19 in Latin America - Lustig, Nora; Martinez Pabon, Valentina; Neidhöfer, Guido (2021)
We simulate the short- and long-term distributional consequences of COVID-19 in the four largest Latin American economies: Argentina, Brazil, Colombia and Mexico. We show that the shortterm impact on income inequality and poverty can be very significant, but that additional spending on social assistance more than offsets the effect in Brazil. The offsetting effect is significant in Argentina and Colombia, and nil in Mexico where there has been no such expansion. We find that a universal basic income that would have produced the same reduction in the poverty gap as actual policies would have cost slightly more but would have benefited the poor (the nonpoor) slightly less (more). To project the long-term consequences, we estimate the impact of the pandemic on school achievement and its intergenerational persistence. We use information on school closures, educational mitigation policies, and account for educational losses related to health shocks and parental job loss. Our findings show that in all four countries the impact is strongly asymmetric and affects particularly the high-school completion rates of children from disadvantaged families. Our simulations suggest that mitigation policies seem to have a minor impact on containing these negative effects.

Investigating the Activity Levels of School Quality Assurance Officers in Sierra Leone - Beoku-Betts, Iman; Leh Wi Lan (EdTech Hub, 2023)
Since the launch of the Free Quality School Education (FQSE) Programme in 2018, the Sierra Leone Ministry of Basic and Senior Secondary Education (MBSSE) has prioritised the use of data for decision-making across several education reform programmes. Part of this vision has been to build systems to measure school quality through School Quality Assurance Officers (SQAOs) using data collection and feedback. This system includes using tools for teacher management, lesson observations, school improvement, and attendance monitoring. This report presents findings from qualitative research conducted in three districts in Sierra Leone. The aim is to provide the MBSSE and other partners with insights to understand the variation in and what is needed to maximise SQAO activity levels, increase principal engagement with digital tools, and support and promote quality visits to schools. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Education technology in the COVID-19 response in Pakistan - Tabassum, Rabia; Hadi, Murium; Qaisrani, Ayesha; Shah, Qasim (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Country-Level Research Review: EdTech in Pakistan - Zubairi, Asma; Halim, Waqas; Kaye, Tom; Wilson, Sam (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Tanzanian Teachers’ Experiences of Teaching With Technology: Recommendations for policy and practice - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2022)
This policy brief reports on a teacher survey in Tanzania (July–November 2021) that EdTech Hub commissioned HakiElimu to conduct in order to inform the government’s ongoing national school-based TCPD reform. The survey items were taken from a landmark global survey of 20,000+ teachers’ reflections, experiences, and challenges concerning EdTech access and use, teaching and learning, and professional development over the preceding year, reported by a team from T4 Education and EdTech Hub. Keywords: Educational technology; learning outcomes; teacher needs; teacher professional development; teacher voice; technology access An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Telephone Survey: Caregivers' and Learners' Perspectives on SMS for Education in Kenya - Myers, Christina; Jordan, Katy; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia; Zhao, Annette (EdTech Hub, 2022)
This document presents the structure and questions used for a telephone survey which was undertaken with a sample of learners who use the M-Shule platform and their caregivers, in Kenya, during July and August 2022. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teacher Performance-Based Incentives and Learning Inequality - Filmer, Deon; Habyarimana, James; Sabarwal, Shwetlena (Rise Programme, 2020)
This study evaluates the impacts of low-cost, performance-based incentives in Tanzanian secondary schools. Results from a two-phase randomized trial show that incentives for teachers led to modest average improvements in student achievement across different subjects. Further, withdrawing incentives did not lead to a “discouragement effect” (once incentives were withdrawn, student performance did not fall below prebaseline levels). Rather, impacts on learning were sustained beyond the intervention period. However, these incentives may have exacerbated learning inequality within and across schools. Increases in learning were concentrated among initially better-performing schools and students. At the same time, learning outcomes may have decreased for schools and students that were lower performing at baseline. Finally, the study finds that incentivizing students without simultaneously incentivizing teachers did not produce observable learning gains.
Keywords: _B:important; _G:important; _G:reviewed; _Tanzania; _final_bib; _important

Summary: EdTech for Learners With Cognitive and Learning Disabilities - A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Nimra, Afzal (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Learners With Cognitive and Learning Disabilities produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

A Monitoring and Evaluation Framework for Blended Learning: Pakistan Ministry of Federal Education and Professional Training - Khalayleh, Abdullah; Baloch, Imdad; Dele-Ajayi, Opeyemi; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Exploring the Gender Differences in Technology Use for Educational Purposes at Home Among Students in Pakistan - Raza, Oneir; Hennessy, Sara (EdTech Hub, 2025)
This report examines gender disparities in the use of educational technology (EdTech) among students in Pakistan, with the aim of informing policies that foster more inclusive and equitable digital learning environments. Drawing on data from a survey of over 2,000 teachers and interviews with EdTech stakeholders in Islamabad, the report explores how sociocultural norms and parental attitudes shape differential access to and use of EdTech at home—particularly disadvantaging female students. It identifies key barriers including limited access to affordable internet and devices, low digital literacy among parents (especially mothers), and prevailing gender norms that restrict girls’ engagement with technology. The findings highlight an urgent need for targeted interventions that address both infrastructural and sociocultural challenges. Recommendations include: expanding subsidised internet and device access in underserved areas; launching community-based digital literacy programmes for parents; creating safe online spaces for female students; promoting positive gender representation in media; and organising inclusive EdTech initiatives to increase girls’ participation. By tackling these barriers through coordinated action, the report offers a roadmap to bridge the gender gap in EdTech adoption and enhance educational equity in Pakistan. Keywords: EdTech; gender; Pakistan; girls’ education; developing economies; educational technology An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Continue or reboot? Overarching options for education responses to COVID-19 in low- and middle-income countries - Haßler, Björn (2020)
Björn Haßler, https://opendeved.net/2020/04/15/continue-or-reboot/, 2020-04-15, DOI: 10.5281/zenodo.3753513
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _yl:p; _zenodoETH; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 2: Insights from user research - Rahman, Asad; Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the second of five reports on the development of a proof of concept for the Hub. It provides a summary of user research undertaken for the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest. Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Technology use for teacher professional development in low- and middle-income countries: A systematic review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (Computers and Education Open, 2022)
Pre-service education and in-service teacher professional development (collectively termed teacher professional development or TPD here) can play a pivotal role in raising teaching quality and, therefore, learning outcomes for children and young people in low- and middle-income countries (LMICs). However, TPD opportunities in LMICs are limited, unsustained, and often not informed by recent research evidence, and outcomes are mixed. Educational technologies offer potential to enhance formally provided programmes and informal peer-learning forms of TPD. We present the first systematic review of the literature pertaining to technology-mediated TPD for educators of school-aged learners in LMICs, aiming to characterise appropriate and effective uses of technology along with specific constraints operating in those contexts. An in-depth synthesis of 170 studies was undertaken, considering macro-, meso- and micro-level factors during TPD design and implementation in the 40 LMICs represented. Volume of publications increased dramatically over the review period (2008–2020), indicating that the field is rapidly developing. Results largely showed benefits for teachers, but evidence for sustainability, cost-effectiveness or tangible impacts on classroom practice and student outcomes was thin. Promising, locally-contextualised forms of technology-mediated TPD included virtual coaching, social messaging, blended learning, video-stimulated reflection, and use of subject-specific software/applications. We report on the variable effectiveness of programmes and limited attention to marginalised groups. To maximise effectiveness of technology-enhanced TPD, the role of facilitators or expert peers is paramount – yet often glossed over – and the interpersonal dimension of teacher learning must be maintained. Recommendations are made for researchers, policymakers, teachers and teacher educators.
Keywords: ICT; Teacher professional development; e-learning; low- and middle-income countries (LMICs); pedagogy; peer learning; teacher training; technology

Technology use for teacher professional development in low- and middle-income countries: A systematic review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (Computers and Education Open, 2022)
Pre-service education and in-service teacher professional development (collectively termed teacher professional development or TPD here) can play a pivotal role in raising teaching quality and, therefore, learning outcomes for children and young people in low- and middle-income countries (LMICs). However, TPD opportunities in LMICs are limited, unsustained, and often not informed by recent research evidence, and outcomes are mixed. Educational technologies offer potential to enhance formally provided programmes and informal peer-learning forms of TPD. We present the first systematic review of the literature pertaining to technology-mediated TPD for educators of school-aged learners in LMICs, aiming to characterise appropriate and effective uses of technology along with specific constraints operating in those contexts. An in-depth synthesis of 170 studies was undertaken, considering macro-, meso- and micro-level factors during TPD design and implementation in the 40 LMICs represented. Volume of publications increased dramatically over the review period (2008–2020), indicating that the field is rapidly developing. Results largely showed benefits for teachers, but evidence for sustainability, cost-effectiveness or tangible impacts on classroom practice and student outcomes was thin. Promising, locally-contextualised forms of technology-mediated TPD included virtual coaching, social messaging, blended learning, video-stimulated reflection, and use of subject-specific software/applications. We report on the variable effectiveness of programmes and limited attention to marginalised groups. To maximise effectiveness of technology-enhanced TPD, the role of facilitators or expert peers is paramount – yet often glossed over – and the interpersonal dimension of teacher learning must be maintained. Recommendations are made for researchers, policymakers, teachers and teacher educators.
Keywords: ICT; Teacher professional development; e-learning; low- and middle-income countries (LMICs); pedagogy; peer learning; teacher training; technology

EdTech in Nigeria: A Rapid Scan. An overview of EdTech policies and interventions in Nigeria with a focus on northern Nigeria - Ramesh Vasudevan, Sharanya; Oyedele, Oluwatomisin (EdTech Hub, 2024)
Commissioned as a Helpdesk request from the FCDO-funded Partnership for Learning for All in Nigeria (PLANE) project, this EdTech Hub rapid scan provides an overview of the EdTech landscape in Nigeria. Given the PLANE programme’s focus on northern Nigeria, this rapid scan also assesses state-level policies and infrastructural challenges in three northern Nigerian states — Jigawa, Kaduna, and Kano. Furthermore, this rapid scan builds on the evidence presented in the previous EdTech Hub rapid scan from 2020, which focused on all states and the situation before the Covid-19 pandemic. Keywords: EdTech; policies; interventions; northern Nigeria; Partnership for Learning for All in Nigeria An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 5: Final report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021, the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE), and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fifth and final report on the development of a proof of concept for the Regional Learning Hub. We recommend beginning with this document and then moving to any of the remaining four reports, depending on your interest: Inception report; User research; Skills taxonomy; Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Child-directed Tablet-based Learning: Toolkits for project design, preparation, and implementation - Imagine Worldwide (2020)

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Can A/B Testing at Scale Accelerate Learning Outcomes in Low- and Middle-Income Environments? - Friedberg, Aidan (Springer Nature Switzerland, 2023)
On current trends the world will fail to reach the objectives set in the UN’s Sustainable Development Goals for Education by 2030 or even within the 21st century. Changing this trend will require a significant acceleration in learning outcomes. Digital personalised learning (DPL) tools are a potentially cost-effective intervention that can contribute to this acceleration. In particular, the continuous experimentation afforded by these tools through software A/B testing, has considerable potential to create compounding improvements in learning outcomes. This paper provides an overview of EIDU, an educational platform combining student focused DPL content with digital structured pedagogy programmes in public pre-primary schools in Kenya. Collection of student’s longitudinal unsupervised assessment data at scale creates the possibility of learning outcome focused A/B testing. This is a novel contribution to the development and research field as up until now this type of capability has largely been confined to students in high-income environments.

Combining school-catchment area models with geostatistical models for analysing school survey data from low-resource settings: Inferential benefits and limitations - Macharia, Peter M.; Ray, Nicolas; Gitonga, Caroline W.; Snow, Robert W.; Giorgi, Emanuele (Spatial Statistics, 2022)
School-based sampling has been used to inform targeted responses for malaria and neglected tropical diseases. Standard geostatistical methods for mapping disease prevalence use the school location to model spatial correlation, which is questionable since exposure to the disease is more likely to occur in the residential location. In this paper, we propose to overcome the limitations of standard geostatistical methods by introducing a modelling framework that accounts for the uncertainty in the location of the residence of the students. By using cost distance and cost allocation models to define spatial accessibility and in absence of any information on the travel mode of students to school, we consider three school catchment area models that assume walking only, walking and bicycling and, walking and motorized transport. We illustrate the use of this approach using two case studies of malaria in Kenya and compare it with the standard approach that uses the school locations to build geostatistical models. We argue that the proposed modelling framework presents several inferential benefits, such as the ability to combine data from multiple surveys some of which may also record the residence location, and to deal with ecological bias when estimating the effects of malaria risk factors. However, our results show that invalid assumptions on the modes of travel to school can worsen the predictive performance of geostatistical models. Future research in this area should focus on collecting information on the modes of transportation to school which can then be used to better parametrize the catchment area models.
Keywords: Catchment area models; Disease mapping; Missing locations; Model-based geostatistics; Prevalence; School survey

Unlocking data to tell the story of education in Africa: webinar summary & synthesis - Adam, Taskeen; Agyapong, Samuel; Asare, Samuel; Heady, Lucy; Wairimu, Wacharia; Mjomba, Renaldah; Mugo, John; Mukiria, Faith; Munday, Gemma (Zenodo, 2020)
[No description available.]
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Testing Digital Timer Tools to Support Early Grade Lesson Delivery - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the second in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates whether introducing a timer alongside digitised lesson plans impacts upon teachers’ lesson plan usage. The A/B test found that providing a timer did not influence how much time teachers spent on digitised lesson plans. While, on average, teachers in the timer group tended to spend less time on lesson plans for literacy and more for numeracy, this was not statistically significant. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; timer; lesson plan An output of EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

Low-connectivity Educational Technology: A Case Study of Supporting Learning during Covid-19 via SMS with ‘Keep Kenya Learning’ - Jordan, Katy; Mumbi, Albina; Khagame, Phoebe; Njuguna, Lydia (Journal of Learning for Development, 2024)
The use of Short Messaging Service (SMS) for education has grown in recent years, drawing particular attention to supporting school-level learners, due to the Covid-19 pandemic. This renewed interest has prompted questions about how this form of educational technology could be used in the longer term. However, despite being used in many Covid-19 responses, there are few documented examples of innovative applications in this field during the pandemic, which represents a gap in the literature. As a medium for education, SMS offers potential benefits such as being cost-effective and having positive impacts on learning. In this paper, we present a case study of an educational programme rapidly implemented during the pandemic as part of the ‘Keep Kenya Learning’ program, to support learners remotely in terms of literacy, numeracy, and social and emotional learning topics. Through the case study, we describe the innovative process used to rapidly develop content for SMS, and draw upon usage statistics, quiz scores and user feedback to gain insights into its implementation with learners and caregivers in Kenya. The case study demonstrated that educational television content can be effectively adapted to mobile delivery. Furthermore, we present practical reflections on the development and implementation of SMS educational technology which will help inform future initiatives. These include considering timing in relation to school terms when planning a supporting intervention, and designing content in a modular way to allow flexibility for learners in navigating through courses.

Supporting equitable access to learning via SMS in Kenya: Impact on engagement and learning outcomes - Jordan, Katy; Myers, Christina; Damani, Kalifa; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia (British Journal of Educational Technology, 2024)
Abstract The use of SMS messaging for education has grown in recent years, with particular attention recently during the Covid‐19 pandemic. Mobile phones often have high levels of ownership in low‐income contexts compared to computers, and lower connectivity requirements, which arguably make this a more equitable medium than data‐heavy online instruction, for example. However, given that gender can be a factor to influence mobile device access and use, it is also important to consider educational applications through a gender lens, to avoid further exacerbating digital divides. In this paper, we present an analysis of server log and evaluation data in relation to a literacy‐focused initiative for primary‐aged learners carried out in Kenya as part of the Tusome programme and through the SMS‐based M‐Shule education platform, which does not require an Internet connection or smartphone to run. The extent of engagement with the platform varies according to gender and location within the country. The data also demonstrate a positive impact on learning outcomes regardless of learners' gender and location. Furthermore, the learning gains are shown to be relatively cost‐effective in comparison with educational technology interventions in similar contexts. The findings show that this low‐connectivity adaptive model has a positive impact on learning outcomes. It is a scalable approach to support a range of learners in Kenya, providing more support to learners who need it, and leading to increased foundational learning outcomes overall. As such, the findings will also be of highly relevant to other low‐connectivity contexts. Practitioner notes What is already known about this topic Mobile phones can be used as a means to support learning, through mobile learning and SMS, particularly in low‐connectivity contexts, although there is a lack of rigorous evidence of impact upon learning outcomes. Mobile phone device ownership tends to be higher than computer or wired Internet connections in many low‐income contexts. Software applications which adapt to the learners' level have shown good potential for gender‐equitable learning outcomes in low‐income contexts; however, these often require an Internet connection in addition to computers or tablets to be run on. What this paper adds There is a lack of contextually relevant evidence of the impact of SMS‐based mobile learning applications in low‐resource and low‐connectivity contexts upon learning outcomes. Through analysis of data generated via an experimental design, this study provides evidence that literacy materials delivered through an SMS‐based educational platform—M‐Shule—can have a positive impact upon learning outcomes. Furthermore, gains are equitable in terms of learners' gender, and location, within Kenya. Implications for practice and/or policy Mobile phones can be an effective way of reaching learners to provide additional educational support as part of existing education programmes in low‐connectivity environments. Learning gains using M‐Shule are evidenced as significant and relatively cost‐effective. Existing high‐quality learning materials developed in other media can be effectively adapted to SMS to reach learners particularly who are out‐of‐school or during periods of educational disruption.

Elevating Education at High Altitude: EdTech implementation in Gilgit-Baltistan - Aslam, M. Nawaz; Mazari, Haani; Hayat, Amal; Hassan, Syed Mustafa; Afzal, Nimra; Zahir, Jazib; Ministry of Federal Education and Professional Training, Pakistan (EdTech Hub, 2024)
Gilgit-Baltistan, located in the northernmost part of Pakistan, is a region known for its mountainous geography. Its complex geography creates challenges for education, such as geographic isolation and infrastructural limitations. While technology offers the potential to overcome these barriers of isolation, several infrastructural and capacity barriers prevent equitable access to EdTech. The Government of Gilgit-Baltistan has strived to respond to these barriers by introducing a more holistic EdTech implementation model that aims to contextualise solutions toward infrastructural and capacity needs. The study investigates the government’s reforms and initiatives to identify good practices and provide further recommendations to enhance EdTech implementation in Gilgit-Baltistan. It also considers the strengths and opportunities that shape Gilgit-Baltistan’s approaches to implementing EdTech through the 'STEAM' and 'Smart Schools' interventions. Key elements of the government’s approach to implementing EdTech include a focus on aligning intervention design with infrastructural needs, for example, by considering solarisation to improve access to power sources. The introduction of ‘hot spots’ to enable offline access to an LMS has enabled schools to access preloaded, curriculum-aligned teaching and learning materials. To overcome challenges in teacher capacity, the government invested in ‘Tech Fellows’ (IT graduates who support teachers with classroom integration) to bridge the gap between limited digital skills and implementation requirements. In this study, we find areas through which this model can be strengthened and highlight examples that implementers in low-resource settings can learn from. low-resource contexts; blended learning; Pakistan; Gilgit-Baltistan; digital skills; teacher training; solar energy; offline solutions An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Artificial intelligence for strengthening healthcare systems in low- and middle-income countries: A systematic scoping review - Ciecierski-Holmes, Tadeusz; Singh, Ritvij; Axt, Miriam; Brenner, Stephan; Barteit, Sandra (npj Digital Medicine, 2022)
In low- and middle-income countries (LMICs), AI has been promoted as a potential means of strengthening healthcare systems by a growing number of publications. We aimed to evaluate the scope and nature of AI technologies in the specific context of LMICs. In this systematic scoping review, we used a broad variety of AI and healthcare search terms. Our literature search included records published between 1st January 2009 and 30th September 2021 from the Scopus, EMBASE, MEDLINE, Global Health and APA PsycInfo databases, and grey literature from a Google Scholar search. We included studies that reported a quantitative and/or qualitative evaluation of a real-world application of AI in an LMIC health context. A total of 10 references evaluating the application of AI in an LMIC were included. Applications varied widely, including: clinical decision support systems, treatment planning and triage assistants and health chatbots. Only half of the papers reported which algorithms and datasets were used in order to train the AI. A number of challenges of using AI tools were reported, including issues with reliability, mixed impacts on workflows, poor user friendliness and lack of adeptness with local contexts. Many barriers exists that prevent the successful development and adoption of well-performing, context-specific AI tools, such as limited data availability, trust and evidence of cost-effectiveness in LMICs. Additional evaluations of the use of AI in healthcare in LMICs are needed in order to identify their effectiveness and reliability in real-world settings and to generate understanding for best practices for future implementations.
Keywords: Health policy; Translational research

An interactive math braille learning application to assist blind students in Bangladesh - Nahar, L; Sulaiman, R; Jafaar, A (Assistive Technology, 2020)
Due to the lack of affordable assistive tools for learning mathematics, blind students in Bangladesh still use outdated learning tools like Tailor Frame. Therefore, demand for a low-cost technological tool is there that will help the blind students to learn math braille and calculate numbers more easily. To provide an effective and affordable assistive tool, this study begins with a needs assessment study to identify the basic needs of blind students in learning math braille and solving mathematical calculations. Afterward, a mobile phone based interactive assistive application is proposed to improve the learning facilities of math braille using Nemeth code for blind students in Bangladesh. Interfaces of the application are designed based on their needs. Besides, interaction methods (such as, hearing & touching) of blind students with the physical world were another criterion in designing very interactive interfaces that provide self-learning facilities. The interfaces are evaluated by the teachers, experts, and end users in order to identify the usability. The evaluation shows a promising result toward the acceptability of the designed application. Therefore, this application can be helpful for the blind students to learn math braille using Nemeth Code.

Evidence Coaching Handbook - Rahman, Asad (EdTech Hub, 2024)
This handbook captures EdTech Hub's approach to providing evidence coaching on the EdTech Hub Evidence-Led Entrepreneurship Course. Individuals and organisations who support EdTech entrepreneurs to scale their products impactfully (e.g., accelerators, entrepreneurship programmes, funders) can all provide evidence coaching to entrepreneurs. This Handbook is for anyone working within an EdTech startup, or an entrepreneur who wants to better apply evidence to key decisions. By sharing EdTech Hub’s approach and process for evidence coaching, we hope to nurture a more evidence-led EdTech entrepreneurship ecosystem, leading to more EdTech products that scale sustainably, and help children to read, write, and count. The Handbook contains EdTech Hub’s five-step process for generating and applying evidence as a startup, with specific tools we used along the way. The process is a guide for others to adapt and tailor to their unique context and challenges. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech in Ghana: A Rapid Scan - Taddese, A. (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive; however, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Ghana. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: Access; C:Ghana; Distance learning; EdTech; LP: English; Online learning; Remote learning; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH

T-TEL Covid-19 Impact Assessment Study - Ananga, Eric; Kadiri, Abdul-Karim; Kporwodu, Marie; Nkrumah, Yahya; Whajah, Francis; Tackie, Majorie (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted

EdTech in Lao People's Democratic Republic: A Rapid Scan - Afzal, Nimra; Thang, Sarah; Tulivuori, Jukka; Thinley, Sangay; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, and in this case, Lao People’s Democratic Republic (PDR). This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert based at the Australian Council for Educational Research. Keywords: Ministry of Education and Sports; digital skills; training programmes; government expenditure; learning outcomes; disparities An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech Interventions for Deaf Learners: Sprint 2 Review - Rahman, Asad; Siddiqui, Maira; Shaikh, Sarah; Geary, Richard; Awasen, Aaron; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Data Access and Protection Laws in Pakistan: A technical review - Halim, Waqas; Upadhyay, Arjun; Coflan, Caitlin (EdTech Hub, 2022)
The advancement of technologies has supported an exponential rise in the collection and use of data. Data, when used appropriately, can support better decision-making and inform innovation. Data has value to entrepreneurs and innovators who seek to design products that respond to user needs. However, the widespread collection and use of data have also spawned concerns about individual rights and data privacy. Issues related to collection, usage, dissemination, and access to data have also come to the forefront. To address these concerns, many countries across the globe have introduced data protection laws. This policy brief identifies and analyses global best practices in data protection and data access. It is developed in response to an inquiry related to data and research in the education sector, specifically in Pakistan. The brief explores the potential practical challenges in the enforcement and implementation of global good practices in the context of the data protection environment in Pakistan; it proposes a set of key recommendations for the Government of Pakistan, provincial governments, development partners, and other education-related ministries and public departments. Keywords: Data protection (laws), good practices, data access, privacy rights, children's data, sensitive data, data-driven policy, data integration, third-party data sharing, open data, data security, data governance, encryption An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech in Nigeria: A Rapid Scan - Dele-Ajayi, Opeyemi; Taddese, Abeba (EdTech Hub, 2020)
Keywords: C:Nigeria; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

STEM Skills Initiatives for Adolescent Girls in the LAC Region - Villavicencio, Xuzel; Myers, Christina; Coflan, Caitlin Moss (EdTech Hub, 2022)
This report was produced in response to a request from the UNICEF country office of Argentina and presents a curated list of science, technology, engineering, and mathematics (STEM) skills initiatives for adolescent girls in the Latin American and Caribbean (LAC) region. It also provides an introduction to gender equality and background on the participation of women in STEM fields in the LAC region — as well as cross-cutting recommendations based on an analysis of a series of initiatives. Key words: STEM; Gender; Girls; LAC; Argentina; technology; Science An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _r:AddedByZotZen

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech in Cambodia: A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Cambodia. This report was originally written in January 2024. It is based primarily on desk research, with quality assurance provided by a country expert — an Education Specialist with the UNICEF Cambodia office. Keywords: out-of-school populations; girls and gender; Southeast Asia; learners with special educational needs and disabilities; primary education; secondary education An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Harnessing EdTech for Neurodivergent Learners in LMICs: A Rapid Evidence Synthesis - Layachi, Aida; Plaut, Daniel (EdTech Hub, 2025)
As neurodivergent learners continue to face multifaceted challenges that affect their education, education systems, environments, and practices have struggled to address their needs adequately. This rapid evidence synthesis explores the current state of evidence regarding the use of educational technologies (EdTech) for neurodivergent learners in low-and middle-income countries (LMICs). The review was conducted in two phases to offer complementary insights on the topic. The first phase presents the findings regarding the use of EdTech for neurodivergent learners in LMICs. The second phase expands the focus, offering evidence and examples that extend beyond LMICs, providing a global perspective on how EdTech could be applied and adapted to LMICs to address different challenges faced by neurodivergent learners. The holistic framework for EdTech for neurodivergence presented in this synthesis provides insights and recommendations regarding the potential of EdTech in optimising systems, environments, and education practices. Keywords: EdTech, Neurodivergence, LMICs, holistic framework, learners An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Education technology in the COVID-19 response in Nigeria - Isisi, Akogun; Olojede, Omolola; Adedoyin, Adesina; Akogun, Oladele (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

The Power of Girls' Reading Camps: Exploring the impact of radio lessons, peer learning and targeted paper-based resources on girls’ remote learning in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Njeri, M.E.; Naylor, Ruth; Page, Ella; Riggall, Anna (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

One Teacher Thailand: A case study of a teacher learning network - Thang, Sarah; Thinley, Sangay; Wiboonuppatum, Rangsun; Saihjee, Aarti; Khlaisang, Jintavee; Thammetar, Thapanee; Kaosaiyaporn, Ophat; Saiyasit, Pichsinee; Theeraroungchaisri, Natchapat (EdTech Hub, 2025)
This case study explores One Teacher Thailand (OTT), a teacher-led learning network that supports holistic professional development rooted in the real needs of classrooms. Driven by a core team of volunteer teacher leaders, OTT integrates educational technology with broader concerns such as mental health, safety, and student engagement. The report examines the network’s evolution, identifies key factors behind its success, and offers recommendations to guide its continued growth and scaling across Thailand. Keywords: teacher networks; Thailand; peer learning; teacher leadership; teacher professional development A version of this report in Thai has been published by UNICEF and available by following the link to this provided with this record below. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

How to Design EdTech Programmes That Lead to Gender-Transformative Change - Samuels, Fiona; Leon-Himmelstine, Carmen; Marcus, Rachel; Myers, Christina (EdTech Hub, 2022)
This paper outlines how EdTech programming can adopt a gender-transformative approach to improve gender equity in access and learning outcomes. It explains what the term ‘gender-transformative change’ means, and why it is needed. Some key dimensions of gender-transformative approaches in the specific context of EdTech initiatives are outlined, looking at how different approaches can enhance access to education and learning opportunities and improve outcomes, and challenge discriminatory gender norms and stereotypes. Based on a desk review of grey and published materials, this paper then presents and discusses insights from the approaches taken by four EdTech programmes. Keywords: EdTech; gender-transformative; country case studies; education; girls’ education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech in Timor-Leste: A Rapid Scan - Honda, Delanie; Thinley, Sangay; Thang, Sarah; Flam, Rebekka; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Timor-Leste. This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert at the Australian Council for Educational Research. Keywords: out-of-school children and youth; girls' education; Southeast Asia; learners with special education needs and disabilities; digital education An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Girls’ Education and EdTech: A Rapid Evidence Review - Webb, Daniel; Barringer, Katie; Torrance, Rebecca; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of technology in supporting girls’ education in low and middle-income countries (LMICs). The RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread global shutdown of schools. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations to the continuation of schooling caused by COVID-19. Established approaches to maintaining continuity of education for the most marginalised have particular salience during this period because of the significant increase in the number of students at risk of disruption. Research consistently shows that while education across the board is negatively affected by crisis situations, the schooling of girls is disproportionately impacted. The RER aims neither to advocate nor discourage the use of technology in girls’ education in response to the present COVID-19 pandemic, but rather to provide an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential role of technology in delivering education for girls.
Keywords: L:English UXZJW5DR; L:Gender and education; LP: English; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; ⛔ No DOI found; ⛔ No INSPIRE recid found

Responding to autism in low and middle income countries (LMIC): What to do and what not to do - McConkey, Roy (Brain Sciences, 2022)
Autism is a spectrum disorder that occurs globally with increasing numbers of children and adults being identified with this condition. Although rates are higher in more affluent nations, the bulk of people with autism reside in Low and Middle Income Countries (LMICs). However, most do not have access to timely and appropriate support. The types of services delivered in high income countries are often ill-suited to the needs and resources of LMICs. Rather alternative forms of provision need to be devised. In common with other public health initiatives, these should be family-focused and community based, with suitably qualified and experienced leaders who in turn train and supervise a cadre of knowledgeable support workers drawn from local communities and cultures. As well as providing personalized, home-based guidance to people with autism and to their primary carers, regular group-based advocacy and training activities are undertaken in partnership with available mainstream services such as schools and social services. The principles and operations of these new forms of services are described in this paper albeit with an acknowledgment of their limitations. In recent decades, the cost-effectiveness of these approaches have been demonstrated with other chronic illnesses and disabling conditions in LMICs but their extension to autism has barely begun. More affluent countries are being forced to adopt similar strategies in response to the increased numbers of people identified with autism. A transformation in research strategies is essential to building better international support for persons with autism.

The last mile in school access: Mapping education deserts in developing countries - Rodriguez-Segura, Daniel; Kim, Brian Heseung (Development Engineering, 2021)
With recent advances in high-resolution satellite imagery and machine vision algorithms, fine-grain geospatial data on population are now widely available: kilometer-by-kilometer, worldwide. In this paper, we showcase how researchers and policymakers in developing countries can leverage these novel data to precisely identify “education deserts” – localized areas where families lack physical access to education – at unprecedented scale, detail, and cost-effectiveness. We demonstrate how these analyses could valuably inform educational access initiatives like school construction and transportation investments, and outline a variety of analytic extensions to gain deeper insight into the state of school access across a given country. We conduct a proof-of-concept analysis in the context of Guatemala, which has historically struggled with educational access, as a demonstration of the utility, viability, and flexibility of our proposed approach. We find that the vast majority of Guatemalan population lives within 3 km of a public primary school, indicating a generally low incidence of distance as a barrier to education in that context. However, we still identify concentrated pockets of population for whom the distance to school remains prohibitive, revealing important geographic variation within the strong country-wide average. Finally, we show how even a small number of optimally-placed schools in these areas, using a simple algorithm we develop, could substantially reduce the incidence of education deserts in this context. We make our entire codebase available to the public – fully free, open-source, heavily documented, and designed for broad use – allowing analysts across contexts to easily replicate our proposed analyses for other countries, educational levels, and public goods more generally.
Keywords: Access to education; Education deserts; Education in developing countries; School placement

A Work Plan for Content Creation - Groeneveld, Caspar; Kibga, Elia; Proctor, Jamie; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Community Help for Inclusive Learning and Development (CHILD): A Study of How Mobile Phones Were Used to Recruit and Equip Community Volunteers to Support Children’s Learning During Covid-19 School Closures in Zimbabwe - Power, Tom; Buckler, Alison; Ebubedike, Margaret; Tengenesha, Martha; Jama, Mbuso; Ndlovu, America; Mukoyi, Jane; Ndou, Mashudu; Mubaira, Simbarashe (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 1: Inception Report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the first of five reports on the development of a proof of concept for the Hub. It provides a background and overview of the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

COVID-19 and the education response in Indonesia: exploring the learning crisis - Suriastini, Wayan; Setyo, Pujiastuti; Herawati, Fita; Naryanta; Moddilani, Ganiko; Pellini, Arnaldo (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

EdTech in Malawi: A Rapid Scan - Rui, Yang (Tingting) (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but not exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Malawi. Keywords: Malawi, EdTech, Policy, ICT An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

EdTech Policy Rapid Scan for Sub-Saharan Africa - Flam, Rebekka; Oyedele, Oluwatomisin (EdTech Hub, 2025)
This rapid scan presents a curated list of EdTech policies in sub-Saharan Africa, compiled in response to a request from the World Bank. Based on desk research from mid-2024, it highlights that most policies predate COVID-19, with few new ones emerging post-2020. Many countries lack dedicated EdTech policies, instead relying on broader ICT or education strategies. Common themes include digital infrastructure, distance learning, and teacher training, while gaps remain in support for marginalised learners. The report provides an overview of existing policies, while the highlighted trends offer insights for future policy development. Keywords: EdTech policy; education policy; sub-Saharan Africa; EdTech governance; digital learning; digital infrastructure An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 4: Content curation - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fourth of five reports on the development of a proof of concept for the Hub and describes our observations during content curation. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Lack of Means or Lack of Awareness? Survey findings: barriers to learning with WhatsApp in refugee camps in Lebanon - Boujikian, Michèle; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

Overview of Emerging Country-Level Response to Providing Educational Continuity Under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
Keywords: ⛔ No DOI found

A Theory of Change for Parents and Caregivers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Ahmed, Shakil; Mazari, Haani; Kaye, Tom; Radford, Kate; Otieno, Jennifer (EdTech Hub, 2022)
The third of a trilogy of Theories of Change (TOCs) that focuses on parents and caregivers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how parents’ and caregivers’ experiences in diverse programmes and initiatives will enable them to support children to improved educational outcomes, and take advantage of available technology. It offers a tool for programme designers, implementers, and evaluators to think critically about how their initiative(s) will impact parents and caregivers for the longer-term benefits of their children. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; parents and caregivers; parenting; education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

National Framework for Teachers Continuous Professional Development - Ministry of Education, Science and Technology (United Republic of Tanzania, 2020)

Child-directed Tablet-based Learning: Project Preparation Toolkit - Imagine Worldwide (2020)

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Government of Sierra Leone Education Data Hub: A User Research Report - Freiermuth, Sophie; Bedoui, Claire; Middleton, Emily; Taddese, Abeba (EdTech Hub, 2020)
Report on the Government of Sierra Leone Education Data Hub
Keywords: C:Sierra Leone; ES:Educational data; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
Keywords: auto_merged

Designing Teacher Learning Circles for Improved Foundational Numeracy Outcomes: Findings from the National Numeracy Programme in Malawi - Correa de Oliveira, André; Plaut, Daniel; Kanyoza, Charity; Boilo, Violet; Chidothi, Emmanuel; Kadzamira, Esme; Mpoola, Dorothy; McBurnie, Chris; Phiri, Magret; Haßler, Björn (EdTech Hub, 2024)
The Malawi National Numeracy Programme (NNP) was designed in 2020 in partnership with the Malawi Ministry of Education and Cambridge Education (Mott McDonald), funded by the UK Foreign, Commonwealth and Development Office (FCDO). Building on findings from a prior qualitative review of the NNP's programme components, EdTech Hub proposed a new phase of design-based implementation research (DBIR) to be undertaken in Term 2 of the 2022–2023 school year to refine the school-based teacher continuous professional development (TCPD) model of the NNP. As part of the research, EdTech Hub developed a new TLC guide to be tested in schools. Through observations, focus group discussions, and interviews, the Hub gathered teacher feedback and used it to co-design and iterate on this guide alongside teachers. This report summarises the principal findings from the study. It also outlines the research background, methodology, findings, and recommendations for the programme moving forward. Keywords: teacher continuous professional development, teacher learning circles, National Numeracy Programme (NNP), Malawi, design-based implementation research An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teaching and Learning of Mathematics in the Context of the National Numeracy Programme in Malawi: Findings from a rapid in-depth qualitative study - Correa de Oliveira, André; Kanyoza, Charity; Smart, Theresa; Lurvink, Anne-Fleur; Boilo, Violet; Kadzamira, Esme; Haßler, Björn (EdTech Hub, 2024)
To inform the development of Malawi's National Numeracy Programme (NNP), EdTech Hub worked with the Directorate of Quality Assurance Services (Malawi), Cambridge Education, and the UK Foreign, Commonwealth and Development Office (FCDO) to examine the NNP’s components during its extended pilot phase during the 2022–2023 school year, and explore how these might be refined to improve teaching and learning of mathematics in Malawi. In-depth qualitative research in four schools was undertaken to obtain feedback on the programme’s components from teachers, head teachers, and Primary Education Advisors. The study’s methodology incorporated semi-structured interviews, focus group discussions, lesson observations, learning circle observations, training observations, and ethnographic methods. Additionally, a mathematics specialist conducted an independent, in-depth, desk-based review of the NNP teaching and learning resources to refine the study’s analysis. This report summarises the principal findings from the study. Keywords: Malawi, mathematics, numeracy, teacher continuous professional development, teacher learning circles An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

National Digital Learning Strategy for the Sierra Leone Ministry of Basic and Senior Secondary Education & Teaching Service Commission 2025–2030 - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2025)
Sierra Leone launches first-ever National Digital Learning Strategy The Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC) are pleased to announce the launch of Sierra Leone’s first-ever National Digital Learning Strategy (NDLS) — a groundbreaking framework aimed at leveraging educational technology to improve teaching and learning in Sierra Leone. Developed through a collaborative and consultative process with representatives from the MBSSE, TSC, Ministry of Tertiary and Higher Education (MTHE), Presidential Delivery Unit (PDU), and Ministry of Communications, Technology, and Innovation (MoCTI) and shaped by insights from students, teachers, district leaders and officials, the NDLS outlines key priorities related to addressing the digital divide in Sierra Leone; improving teachers’ digital capabilities; strengthening learners’ access to technology; improving access to localized content, and improving coordination mechanisms between all EdTech stakeholders. EdTech Hub is a proud partner of this work alongside the UK Foreign, Commonwealth and Development Office (FCDO), UNICEF, the World Bank, and other collaborators. This collaboration included technical guidance and support throughout the process. The NDLS represents a collective commitment to transforming education and building future-ready learners and educators.

What can be learnt from China’s recent experiences with Covid-19 and school closures that can inform other countries’ education technology-enabled responses? - Hallgarten, Joe; Fitzpatrick, Rachael (Education Development Trust, 2020)

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Teachers need training and support, not just an internet connection, to deliver quality distance education - Conover, Anna C (Teacher Task Force, 2022)
This blog is based on the findings of Distance learning and teacher training strategies. Lessons from the Caribbean, a recently published report by the Teacher Task Force. It was written by Anna C. Conover, Consultant Distance teaching and learning have expanded rapidly around the world since COVID-19 school closures first began in 2020. The transition exposed a wide digital divide in many countries, where lack of access to devices, online content and internet connectivity hindered universal access. Equally crucial, the shift shone a light on the need for more and better teacher training in digital and relevant pedagogical skills. However, in spite of this urgent need, ministries of education in many countries are only now integrating ICT competencies and standards into teacher policy frameworks. Moreover, traditional teacher training programmes do not necessarily adequately cover digital and related pedagogical skills in initial teacher training and continuing professional education. Teacher training can help improve learners’ and teachers’ experience of distance learning In response to the demand for training in distance learning and technology integration in small island developing states (SIDS) in the Caribbean, the Distance Learning and Teacher Training Strategies in the Caribbean SIDS teacher training programme was created to enhance the capacity of national education systems. The Teacher Task Force, UNESCO’s Global Education Coalition, Blackboard, the Caribbean Centre for Educational Planning (CCEP), UNICEF Jamaica, and the German Federal Ministry for Economic Cooperation and Development collaborated to develop, implement and monitor the programme. Building on the 2020 pilot project, Professional Development for Teachers for Blended Learning and Online Strategies, the programme was designed to strengthen teachers’ digital and related pedagogical skills. It took a holistic and context-sensitive approach to strengthening teachers’ capacity to guarantee that the most vulnerable students were not left behind during the crisis. The project aimed to confront challenges such as: how to maintain engagement and interaction for learning; how to convert content into appropriate online learning formats; how to handle school management issues, such as the need to respect normal school hours; and how to work with students with diverse needs. Providing support in these areas also helped to address teachers’ psychosocial well-being, since the abrupt transition to online teaching led to significant disruption of teachers’ professional and personal lives, causing uncertainty and other emotional challenges. Careful course design, adaptable materials and supportive communities of practice are essential for successful distance learning A key lesson from the programme was the importance of high standards for course design, content, and capacity for collaboration and delivery. Online platforms or learning management systems must be intuitive and user-friendly; courses must include different forms of interaction and student-teacher feedback loops; and time and space must be allotted for collaboration, reflection and experimentation. Since parental involvement is important for successful distance learning, course design should also include guidance for parents and reliable channels for them to communicate with teachers. Preparing and adapting materials for online learning is one of the most challenging and time-consuming tasks for teachers in transitioning to distance learning. So, teacher training should include guidance on tools to facilitate this work, such as “live worksheets”, which are interactive and support assessment at a distance. And programmes should use open-source materials where possible, or explicitly state copyright conditions when needed, to increase scalability and enable teachers to re-use materials. Teachers who participated in the teacher training programme particularly appreciated being part of a community of practice, enabling them to make new connections with distance education experts and other teachers in similar situations across their country and region. This feeling of belonging to a supportive network, as well as their newly acquired skills, boosted their personal and professional confidence in applying digital technologies and the required skills in their classrooms. Teacher training for distance education should prepare teachers to create inclusive online learning environments Ensuring inclusive education should be a priority in distance learning. Even though this form of schooling can limit teachers’ interactions with students (e.g., by reducing opportunities for spontaneous communication and gestural cues), it can also provide opportunities to promote inclusion. Designing courses with accessibility in mind is essential to create inclusive learning environments. For instance, to accommodate the needs of learners with disabilities, participants should be given a range of ways to access materials and participate in courses. This may include offering asynchronous* and synchronous** options for discussion, multimodal (visual, aural, textual, etc.) delivery of content, and downloadable as well as livestreamed content. In multilingual contexts, adapting to teachers’ language needs is also essential. In the SIDS programme, course content was often only available in French or English. However, to allow participants to conduct discussions in the language with which they were most comfortable, course facilitators allowed participants to form online breakout groups using other languages. Flexibility is a key feature in planning for teacher training Training teachers for distance education must be flexible, since teachers have competing and sometimes unforeseen demands on their time. Course content, pacing and assignments should be adjusted throughout the course according to participants’ changing needs. This is particularly important during emergency situations. For accreditation transparency and to maintain teacher motivation, courses can adapt to teachers’ time constraints by offering different levels of certification and micro-credentials for specific ICT skills. Careful planning that considers school calendars and teachers’ accessibility needs, as well as good communication campaigns, are essential to ensure successful enrolment and sustained attendance in teacher training. Registration should be easy and obstacle-free, and directly available online. In general, teacher training should not be scheduled at the beginning or at the end of the school year when teachers are busiest, or during long summer vacations when many teachers are not available. Partnerships are important for developing teacher training programmes for distance education Partnerships are particularly important in delivering distance education, since it requires considerable expertise and resources, including costly devices, uninterrupted connectivity, education software, open educational resources, and pedagogical and organizational expertise. Given that connectivity and device availability are often a barrier in online education, governments and stakeholders should develop partnerships with technology companies and internet providers to identify solutions, while ensuring that data security and participant privacy are respected. Educational technologies have proven to be useful to ensure continuity of education in emergency situations. Increasingly true to all societies, they are also among the basic tools needed to fully participate in our contemporary world. However, investing in these technologies will not achieve the desired results unless we also invest in teachers’ digital and related pedagogical skills. Initial and in-service teacher education must therefore be re-imagined including these skills and technologies. With their first-hand experience of the challenges and opportunities of remote teaching, teachers must be involved in the design, implementation and monitoring of distance learning and technology integration. In such a way, they must effectively be placed at the heart of wider education transformation. Glossary  *Asynchronous online learning:  Education and learning that occur online at a different time compared to when the teacher is instructing. **Synchronous online learning: Education and learning that occur online at the same time, but not in the same place with teachers and/or other learners. Photo credit: Abir Roy Barman/Shutterstock.com

Mapeo y análisis de programas EdTech en América Latina y el Caribe - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
Este documento se elaboró ​​en respuesta a una solicitud de la Oficina Regional de UNICEF para América Latina y el Caribe al Servicio de Asistencia de EdTech Hub en octubre de 2021. El equipo de UNICEF solicitó una lista seleccionada de programas de EdTech en la región de América Latina y el Caribe (ALC) y un análisis de un conjunto de programas preseleccionados con la intención de explorar su potencial para la implementación y el impacto a escala. Este informe no pretende cubrir todos los programas EdTech innovadores en la región de ALC. Más bien, presenta una lista de programas EdTech prometedores y analiza su diseño e implementación con el fin de explorar su relevancia y potencial para lograr un impacto a gran escala. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen